Secondary battery and manufacturing method thereof

JP7652083B2Active Publication Date: 2025-03-27ZEON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021567311
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-15
Publication Date
2025-03-27
Estimated Expiration
2040-12-15

AI Technical Summary

Benefits of technology

【0021】 本発明によれば、サイクル特性に優れた二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652083000005
    Figure 0007652083000005
  • Figure 0007652083000006
    Figure 0007652083000006
  • Figure 0007652083000007
    Figure 0007652083000007
Patent Text Reader

Abstract

This secondary battery has a stack formed by laminating a positive electrode, a separator, and a negative electrode in said order. A central region P, which has a shape similar to a surface Z constituting a bonding surface X between the positive electrode and the separator and / or bonding surface Y between the negative electrode and the separator, the center of which is located at the same position as the center of the surface Z, and which has an area that is 10% of the area of the surface Z, has a resistance A per unit area that is greater than the resistance B per unit area in the region Q of the surface Z other than the central region P.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery and a method for manufacturing the same. [Background technology]

[0002] Secondary batteries such as lithium ion secondary batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Secondary batteries generally include battery components such as a positive electrode, a negative electrode, and a separator that isolates the positive electrode and the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.

[0003] Known structures of secondary batteries include a stacked type in which a positive electrode, a separator, and a negative electrode are alternately stacked, and a wound type in which a long positive electrode, a separator, and a negative electrode are stacked and wound concentrically, etc. Among these, stacked type secondary batteries have been attracting attention in recent years from the viewpoints of excellent energy density, safety, quality, and durability.

[0004] When manufacturing a secondary battery, for example, a battery component having an adhesive material on its surface is manufactured, and the battery component is bonded to another battery component. The battery component having an adhesive material on its surface can be produced by applying an adhesive composition (slurry for secondary batteries) made by dispersing and / or dissolving an adhesive polymer (binder) in a solvent onto the surface of the battery component, and then drying the applied composition (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-27945 A Summary of the Invention [Problem to be solved by the invention]

[0006] Here, in large secondary batteries for vehicles, etc., the battery generates heat during charging and discharging, and there are some parts inside the battery that become locally hot. On the other hand, it is generally known that lithium-ion batteries are prone to deterioration at high temperatures, shortening their lifespan. For this reason, if temperature unevenness occurs inside the battery, some parts will deteriorate locally, shortening the lifespan of the entire battery, and therefore there is a demand to eliminate temperature unevenness inside the battery (lifespan may be referred to as "cycle characteristics" hereinafter).

[0007] However, in the conventional secondary batteries, temperature variations occur inside the battery, so there is room for improvement in the cycle characteristics.

[0008] Therefore, an object of the present invention is to provide a secondary battery which eliminates temperature unevenness inside the battery and has excellent cycle characteristics. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to achieve the above object, and have found that the cycle characteristics of a secondary battery can be improved by making the resistance A per unit area of ​​a central region P, which has a shape similar to the shape of a surface Z, which is at least one of the bonding surface X between the positive electrode and the separator and the bonding surface Y between the negative electrode and the separator, has a center at the same position as the center of the surface Z, and has a predetermined area, larger than the resistance B per unit area of ​​a region Q other than the central region P in the surface Z, and have completed the present invention.

[0010] That is, the present invention aims to advantageously solve the above problems, and the secondary battery of the present invention is a secondary battery having a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order, and is characterized in that a central region P has a shape similar to the shape of a surface Z which is at least one of the bonding surface X between the positive electrode and the separator and the bonding surface Y between the negative electrode and the separator, has a center at the same position as the center of the surface Z, and has an area of ​​10% of the area of ​​the surface Z, and has a resistance A per unit area larger than a resistance B per unit area of ​​a region Q other than the central region P in the surface Z. In this way, by making the resistance A per unit area of ​​the central region P, which has a shape similar to the shape of the surface Z, has a center at the same position as the center of the surface Z, and has the above-mentioned predetermined area, larger than the resistance B per unit area of ​​the region Q other than the central region P in the surface Z, the cycle characteristics of the secondary battery can be improved. In the present invention, the "center of a surface or region" means the "center of gravity of a surface or region." For example, the "center of a surface or region" ("center of gravity of a surface or region") is the "intersection of diagonals" when the shape of the surface or region is a square, rectangle, parallelogram, or rhombus, the "intersection of midlines" when the shape of the surface or region is a triangle, and the "center of a circle" when the shape of the surface or region is a circle. In the present invention, the resistance A per unit area of ​​the central region P and the resistance B per unit area of ​​the region Q other than the central region P on the surface Z can be measured by the method described in the examples of this specification.

[0011] Here, in the secondary battery of the present invention, it is preferable that an adhesive material is present on the surface Z, and a coverage rate E of the adhesive material in the central region P of the surface Z is greater than a coverage rate F of the adhesive material in a region Q other than the central region P of the surface Z. If the coverage rate E of the adhesive material in the central region P of the surface Z is greater than the coverage rate F of the adhesive material in the region Q other than the central region P of the surface Z, the cycle characteristics of the secondary battery can be further improved.

[0012] In addition, in the secondary battery of the present invention, the coverage E is preferably 1.1% or more and 30% or less. If the coverage E of the adhesive material in the central region P of the surface Z is within the above-mentioned range, the cycle characteristics of the secondary battery can be further improved while maintaining good output characteristics of the secondary battery. Furthermore, if the coverage E of the adhesive material in the central region P of the surface Z is within the above-mentioned range, the secondary battery can exhibit sufficiently excellent output characteristics while sufficiently ensuring the adhesive force between the electrode and the separator.

[0013] In the secondary battery of the present invention, the coverage F is preferably 0.3% or more and less than 0.4×E%. If the coverage F of the adhesive material in the region Q other than the central region P of the surface Z is within the above-mentioned range, the secondary battery can exhibit sufficiently excellent output characteristics while ensuring sufficient adhesive strength between the electrode and the separator. In addition, if the coverage F of the adhesive material in the region Q other than the central region P of the surface Z is within the above-mentioned range, the cycle characteristics of the secondary battery can be further improved.

[0014] In addition, in the secondary battery of the present invention, it is preferable that an adhesive material is present on the surface Z, and the coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z. If the coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z, the cycle characteristics of the secondary battery can be further improved.

[0015] Furthermore, in the secondary battery of the present invention, it is preferable that an adhesive material is present on the surface Z, the adhesive material contains a particulate polymer, and the particulate polymer has a core-shell structure including a core portion and a shell portion partially covering the outer surface of the core portion. By using a particulate polymer having a core-shell structure including a core portion and a shell portion partially covering the outer surface of the core portion as the adhesive material, it is possible to sufficiently secure the adhesive force between the electrode and the separator, and to cause the secondary battery to exhibit excellent output characteristics.

[0016] The present invention also aims to advantageously solve the above problems, and the method for producing a secondary battery of the present invention is a method for producing a secondary battery having a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order, and includes a step of applying an adhesive material to a surface Z which is at least one of a bonding surface X between the positive electrode and the separator and a bonding surface Y between the negative electrode and the separator, and is characterized in that a coverage rate E of the adhesive material in a central region P having a shape similar to the shape of the surface Z, a center at the same position as the center of the surface Z, and an area of ​​10% of the area of ​​the surface Z is larger than a coverage rate F of the adhesive material in a region Q other than the central region P of the surface Z. In this way, according to the above-mentioned method for producing a secondary battery of the present invention, a secondary battery having excellent cycle characteristics can be obtained.

[0017] Here, in the method for producing a secondary battery of the present invention, the coverage E is preferably 1.1% or more and 30% or less. If the coverage E of the adhesive material in the central region P of the surface Z is within the above-mentioned predetermined range, the cycle characteristics of the produced secondary battery can be further improved. Also, if the coverage E of the adhesive material in the central region P of the surface Z is within the above-mentioned predetermined range, the produced secondary battery can exhibit sufficiently excellent output characteristics while sufficiently ensuring the adhesive force between the electrode and the separator.

[0018] In addition, in the method for producing a secondary battery of the present invention, the coverage F is preferably 0.3% or more and less than 0.4×E%. If the coverage F of the adhesive material in the region Q other than the central region P of the surface Z is within the above-mentioned predetermined range, the adhesive force between the electrode and the separator can be sufficiently secured, while the produced secondary battery can exhibit sufficiently excellent output characteristics. Furthermore, if the coverage F of the adhesive material in the region Q other than the central region P of the surface Z is within the above-mentioned predetermined range, the cycle characteristics of the produced secondary battery can be further improved.

[0019] Furthermore, in the method for producing a secondary battery of the present invention, it is preferable that the coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z. If the coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z, the cycle characteristics of the produced secondary battery can be further improved.

[0020] In addition, the method for producing a secondary battery of the present invention is characterized in that the adhesive material contains a particulate polymer, and the particulate polymer has a core-shell structure including a core portion and a shell portion partially covering the outer surface of the core portion. By using a particulate polymer having a core-shell structure including a core portion and a shell portion partially covering the outer surface of the core portion as the adhesive material, it is possible to sufficiently secure the adhesive force between the electrode and the separator, and to allow the produced secondary battery to exhibit excellent output characteristics. Effect of the Invention

[0021] According to the present invention, a secondary battery having excellent cycle characteristics can be provided. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1(a) is a front view showing an example of the structure of a laminate in a secondary battery of the present invention, and FIG. 1(b) is a plan view illustrating the positional relationship between the negative electrode and the positive electrode of the laminate shown in FIG. 1(a). [Diagram 2] FIG. 2 is a front view showing a structure of an example of a stack obtained by stacking stacks in the secondary battery of the present invention. [Diagram 3] FIG. 4 is a front view showing the structure of another example of a laminate in the secondary battery of the present invention. [Figure 4] 1 is an explanatory diagram illustrating a central region P and other regions Q on a surface Z. FIG. [Diagram 5] FIG. 4 is an explanatory diagram showing an example of a coating pattern of an adhesive material. [Figure 6] FIG. 11 is an explanatory diagram showing another example of a coating pattern of an adhesive material. [Figure 7]FIG. 2 is an explanatory diagram showing an example of a method for applying an adhesive material to surface Z. [Figure 8] FIG. 1 is a cross-sectional view showing a schematic structure of an example of a particulate polymer. [Figure 9] 3A to 3C are explanatory diagrams showing an example of a process for producing a laminate in the secondary battery of the present invention. [Figure 10] FIG. 10 is an explanatory diagram showing an example of a coater (nozzle head) in FIG. [Figure 11] FIG. 2 is an explanatory diagram showing a manufacturing process of a laminate in an example and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, the secondary battery and the method for manufacturing the secondary battery of the present invention will be described with reference to the drawings. Note that in each drawing, the dimensions of some components are enlarged or reduced for ease of understanding.

[0024] (Secondary battery) The secondary battery of the present invention includes at least a predetermined laminate, and optionally includes an electrolyte and other components. The secondary battery of the present invention can be manufactured, for example, by using the manufacturing method of the secondary battery of the present invention.

[0025] <Laminate> The laminate in the secondary battery of the present invention has a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order. Here, the laminate in the secondary battery of the present invention has, for example, a structure as shown in Fig. 1 or a structure as shown in Fig. 3. The laminates are laminated to form a laminate 200 as shown in Fig. 2, for example, and can be used in a stacked type secondary battery or the like. As shown in FIG. 1 or FIG. 3, the laminate 100, 100A comprises a negative electrode 20, a first separator 10 bonded to one surface of the negative electrode, a positive electrode 40 bonded to the surface of the first separator 10 opposite the negative electrode 20 side, and a second separator 30 bonded to the other surface of the negative electrode 20 or the surface of the positive electrode 40 opposite the first separator side 10. 1(b), in the laminates 100 and 100A, the size of the positive electrode 40 in a plan view is smaller than the size of the negative electrode 20, the first separator 10, and the second separator 30 in a plan view. Specifically, in a plan view, the negative electrode 20 of the laminates 100 and 100A has a first edge 24 and a second edge 25 that face each other in a direction perpendicular to the stacking direction, and the positive electrode 40 is located between the first edge 24 and the second edge 25 when viewed in the stacking direction. Note that the first edge 24 and the second edge 25 are usually edges that correspond to the cutting positions when a long negative electrode raw material is cut to obtain the negative electrode 20.

[0026] Here, the laminate 100 shown in the front view in FIG. 1(a) includes a negative electrode 20, a first separator 10 bonded to one surface of the negative electrode 20 (upper in FIG. 1), a positive electrode 40 bonded to the surface of the first separator 10 opposite to the negative electrode 20 side (upper in FIG. 1), and a second separator 30 bonded to the other surface of the negative electrode 20. In this example, the first separator 10, the negative electrode 20, the second separator 30, and the positive electrode 40 are rectangular in plan view. The negative electrode 20 has a structure in which negative electrode mixture layers 22 and 23 containing a negative electrode active material are formed on both sides of a negative electrode current collector 21, and the positive electrode 40 has a structure in which positive electrode mixture layers 42 and 43 containing a positive electrode active material are formed on both sides of a positive electrode current collector 41. Furthermore, the size of the positive electrode 40 in a planar view is smaller than the size of the negative electrode 20, the first separator 10, and the second separator 30. As shown in FIG. 1(b) showing the positional relationship between the negative electrode 20 and the positive electrode 40 in a planar view, the positive electrode 40 is located between a first edge 24 and a second edge 25 of the negative electrode 20 that face each other in a direction perpendicular to the stacking direction (the left-right direction in FIG. 1(b)), and between a third edge 26 and a fourth edge 27 that are perpendicular to the first edge 24 and the second edge 25 and extend in the left-right direction in FIG. 1(b).

[0027] Moreover, the laminate 100A shown in a front view in FIG. 3 has the same configuration as the laminate 100 shown in FIG. 1, except that the second separator 30 is bonded to the surface of the positive electrode 40 opposite to the first separator 10 side (the upper side in FIG. 3) instead of to the other surface of the negative electrode 20.

[0028] The laminate in the secondary battery of the present invention is not limited to the examples shown in Fig. 1 and Fig. 3. For example, the laminate may have a first separator 10 and a second separator 30 larger in size than the negative electrode 20 in a plan view. Use of a laminate in which the first separator 10 and the second separator 30 are larger than the negative electrode 20 can further improve the safety of the secondary battery.

[0029] <<Face Z, central region P, other regions Q>> Hereinafter, the central region P and a region Q other than the central region P (hereinafter, sometimes referred to as "other region Q") on the surface Z will be described with reference to FIG. Here, surface Z is at least one of surface X where the negative electrode 20 and the first separator 10 are attached to each other and surface Y where the positive electrode 40 and the first separator 10 are attached to each other. 4, central region P has its center (center of gravity) at the same position as center (center of gravity) R of face Z (intersection of diagonals of a rectangle), has a shape similar to the shape of face Z (rectangle), and has an area of ​​10% of the area of ​​face Z. Other region Q is the entire area of ​​face Z other than central region P, and has an area of ​​90% of the area of ​​face Z.

[0030] The secondary battery of the present invention is characterized in that the resistance A per unit area of ​​the central region P is greater than the resistance B per unit area of ​​the other regions Q. In this way, by making the resistance A per unit area of ​​the central region P greater than the resistance B per unit area of ​​the other regions Q, the secondary battery can exhibit excellent cycle characteristics.

[0031] Here, the reason why making the resistance A per unit area of ​​the central region P larger than the resistance B per unit area of ​​the other regions Q can enable the secondary battery to exhibit excellent cycle characteristics is not clear, but is presumed to be as follows. First, in a secondary battery, surface Z generates heat due to the current flow during charging and discharging. Here, in a conventional secondary battery in which the resistance A per unit area of ​​the central region P is equal to or less than the resistance B per unit area of ​​the other regions Q, the central region P generates heat equal to or more than the other regions Q. Of surface Z, the other regions Q close to the ends of surface Z can easily dissipate heat, but the central region P away from the ends of surface Z has difficulty dissipating heat. Therefore, in the above-mentioned conventional secondary battery, the temperature of the central region P becomes higher than that of the other regions Q due to heat storage, which is thought to cause temperature unevenness inside the battery and deteriorate the cycle characteristics of the secondary battery. In contrast, in the secondary battery of the present invention, the resistance A per unit area of ​​the central region P is made larger than the resistance B per unit area of ​​the other regions Q, thereby making it possible to reduce the current density in the central region P during charging and discharging. This makes it possible to reduce the amount of heat generated in the central region P. Therefore, it is presumed that the temperature rise due to heat storage in the central region P can be suppressed, and the temperature unevenness in the central region P and the other regions Q can be reduced, thereby allowing the secondary battery to exhibit excellent cycle characteristics. In addition, the "end of surface Z" refers to an area other than the central region P" of surface Z that has a center at the same position as the center R of surface Z, has a shape similar to the shape of surface Z, and has an area of ​​90% of the area of ​​surface Z.

[0032] The ratio (A / B) of the resistance A per unit area of ​​the central region P to the resistance B per unit area of ​​the other regions Q must be greater than 1, is preferably greater than 1.005, is more preferably greater than 1.01, and is preferably less than 2, and is more preferably less than 1.5. When the ratio (A / B) of the resistance A per unit area of ​​the central region P to the resistance B per unit area of ​​the other regions Q is greater than 1, the cycle characteristics of the secondary battery can be sufficiently improved. On the other hand, when the ratio (A / B) of the resistance A per unit area of ​​the central region P to the resistance B per unit area of ​​the other regions Q is less than 2, the output characteristics of the secondary battery can be improved. The resistance A per unit area of ​​the central region P and the resistance B per unit area of ​​the other regions Q can be adjusted by the coverage of the adhesive material in each region, the type of polymer used as the adhesive material, etc.

[0033] [Adhesive material] Here, an adhesive material is usually present on the surface Z (the bonding surfaces X and Y). The adhesive material is a material that bonds the electrode (positive electrode or negative electrode) and the separator on the bonding surfaces X and Y. Details of the adhesive material will be described later.

[0034] -How to apply adhesive material- The adhesive material can be supplied to the bonding surfaces X and Y in any state, such as a solid state, a molten state, a state dissolved in a solvent, or a state dispersed in a solvent. Among these, the adhesive material is preferably supplied in a state dissolved in a solvent or a state dispersed in a solvent, and more preferably supplied in a state dispersed in a solvent.

[0035] When the adhesive material is supplied to the bonding surfaces X and Y in a state where it is dissolved or dispersed in a solvent, that is, when an adhesive composition containing an adhesive material and a solvent is supplied to the bonding surfaces, the solvent of the adhesive composition is not particularly limited, and for example, water, an organic solvent, and a mixture thereof can be used. The organic solvent is not particularly limited, and examples thereof include cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; ketones such as ethyl methyl ketone and cyclohexanone; esters such as ethyl acetate, butyl acetate, γ-butyrolactone, and ε-caprolactone; nitriles such as acetonitrile and propionitrile; ethers such as tetrahydrofuran and ethylene glycol diethyl ether; alcohols such as methanol, ethanol, isopropanol, ethylene glycol, propylene glycol, and ethylene glycol monomethyl ether; and the like. Among the above, from the viewpoint of efficiently producing the laminate, the solvent is preferably a solvent containing at least one of water and alcohol. At least a part of the solvent may be removed by drying or the like in the process of producing the laminate.

[0036] The application of the adhesive material using a coater (51 to 54 in Figs. 9 and 10) described later can be performed using known coating methods such as the inkjet method, spray method, dispenser method, gravure coating method, screen printing method, etc. Among them, from the viewpoint of easily adjusting the amount and range of the adhesive material to be applied, it is preferable to apply the adhesive material using the inkjet method.

[0037] The adhesive material is applied only to a portion of the bonding surfaces X and Y. Specifically, the adhesive material is arranged (applied) on the bonding surfaces X and Y in a predetermined pattern, such as a stripe pattern, a dot pattern, or a lattice pattern. From the viewpoint of improving the output characteristics of the secondary battery, the adhesive material is preferably arranged (applied) on the bonding surfaces X and Y in a dot pattern.

[0038] Here, the diameter of the dots of the adhesive material arranged in the dot pattern is preferably 10 μm or more, more preferably 20 μm or more, and preferably 100 μm or less, more preferably 80 μm or less. If the diameter of the dots of the adhesive material is equal to or greater than the lower limit, the adhesive strength between the electrode and the separator can be increased. On the other hand, if the diameter of the dots of the adhesive material is equal to or less than the upper limit, the output characteristics of the secondary battery can be prevented from decreasing.

[0039] Hereinafter, a case will be described in which adhesive material is applied to surface Z so that there are two regions, namely, "region S where adhesive material is densely applied" and "region T where adhesive material is sparsely applied." Here, the coverage rate of the adhesive material in the "region S where the adhesive material is densely applied" is greater than the coverage rate of the adhesive material in the "region T where the adhesive material is sparsely applied". In this specification, the "coverage rate of adhesive material" of a certain surface or region refers to the ratio of the area of ​​the portion covered with adhesive material to the total area of ​​the surface or region [(area of ​​the portion covered with adhesive material / total area of ​​the surface or region) x 100 (%)]. Furthermore, in this specification, when an adhesive composition containing an adhesive material and a solvent is supplied to a bonding surface, the "adhesive material" in the "coverage rate of the adhesive material" refers to the adhesive layer composition in a state in which the solvent has been removed by drying or the like.

[0040] The shape of the "region S where the adhesive material is densely applied" is not particularly limited, and can be appropriately set within a range where the desired effect of the present invention can be obtained. That is, the "region S where the adhesive material is densely applied" can have any shape as long as the resistance A per unit area of ​​the central region P described above is greater than the resistance B per unit area of ​​the other regions Q. The "region T where the adhesive material is sparsely applied" refers to the entire region of the surface Z other than the "region S where the adhesive material is densely applied."

[0041] From the viewpoint of further improving the cycle characteristics of the secondary battery, it is preferable to set the shape of the "region S where the adhesive material is densely applied" so that the coverage rate E of the adhesive material in the above-mentioned central region P is greater than the coverage rate F of the adhesive material in the other regions Q.

[0042] For example, from the viewpoint of further improving the cycle characteristics of the secondary battery, it is preferable that the "region S where the adhesive material is densely applied" includes the center of the surface Z, and it is more preferable that the center be located at the same position as the center of the surface Z.

[0043] In addition, the shape of the "region S where the adhesive material is densely applied" may or may not be similar to the shape of surface Z, but from the viewpoint of further improving the cycle characteristics of the secondary battery, it is preferable that the shape be similar to the shape of surface Z.

[0044] The ratio of the area of ​​the "region S where the adhesive material is densely applied" to the entire area of ​​the surface Z is preferably 5% or more, more preferably 10% or more, preferably 60% or less, more preferably 40% or less, and even more preferably 30% or less. If the ratio of the area of ​​the "region S where the adhesive material is densely applied" to the entire area of ​​the surface Z is within the above-mentioned specified range, the cycle characteristics of the secondary battery can be further improved. Also, if the ratio of the area of ​​the "region S where the adhesive material is densely applied" to the entire area of ​​the surface Z is equal to or less than the above-mentioned upper limit, the output characteristics of the secondary battery can be ensured to be sufficiently high.

[0045] Furthermore, the ratio of the area of ​​the "region T where the adhesive material is sparsely applied" to the entire area of ​​surface Z is preferably 40% or more, more preferably 60% or more, even more preferably 70% or more, and preferably 95% or less, and more preferably 90% or less. If the ratio of the area of ​​the "region T where the adhesive material is sparsely applied" to the entire area of ​​surface Z is within the above-mentioned specified range, the cycle characteristics of the secondary battery can be further improved. Furthermore, if the ratio of the area of ​​the "region T where the adhesive material is sparsely applied" to the entire area of ​​surface Z is equal to or greater than the above-mentioned lower limit, the output characteristics of the secondary battery can be ensured to be sufficiently high.

[0046] The coverage rate J of the adhesive material in the "region S where the adhesive material is densely applied" is not particularly limited as long as it is greater than the coverage rate K of the adhesive material in the "region T where the adhesive material is sparsely applied", but is preferably 1.1% or more, more preferably 3% or more, preferably 30% or less, more preferably 10% or less, and even more preferably 8% or less. If the coverage rate J of the adhesive material in the "region S where the adhesive material is densely applied" is equal to or greater than the lower limit, the cycle characteristics of the secondary battery can be further improved. Also, if the coverage rate J of the adhesive material in the "region S where the adhesive material is densely applied" is equal to or less than the upper limit, the output characteristics of the secondary battery can be sufficiently high.

[0047] In addition, the coverage rate K of the adhesive material in the "region T where the adhesive material is sparsely applied" is not particularly limited as long as it is smaller than the coverage rate J of the adhesive material in the "region S where the adhesive material is densely applied", but is preferably 0.3% or more, more preferably 0.5% or more, and preferably less than 0.4 x J%. If the coverage rate of the adhesive material in the "region T where the adhesive material is sparsely applied" is equal to or higher than the lower limit, the adhesive strength between the electrode and the separator can be sufficiently ensured. In addition, if the coverage rate K of the adhesive material in the "region T where the adhesive material is sparsely applied" is less than the upper limit, the cycle characteristics of the secondary battery can be sufficiently improved.

[0048] The coverage rate of the adhesive material in each of the "area S where the adhesive material is densely applied" and the "area T where the adhesive material is sparsely applied" can be adjusted by changing the arrangement pattern of the adhesive material arranged (applied) in each of the areas.

[0049] Specifically, when adhesive material is arranged (applied) in a dotted pattern in a certain area, the coverage rate of the adhesive material in that area can be adjusted by changing the radius and center-to-center distance of the dots of adhesive material. For example, in an area where an adhesive material is applied (coated) in a dot pattern in which dots are formed at regular intervals in two perpendicular directions as shown in FIG. 5, the coverage rate of the adhesive material can be calculated by the following formula (1) using the center-to-center distances (pitch) x and y of the dots and the radius r of the dots. Adhesive material coverage = {πr 2 / (x y)}×100(%) ···(1)

[0050] Furthermore, in a certain region, when the adhesive material is arranged (coated) in a striped pattern, the coverage rate of the adhesive material in that region can be adjusted by changing the line width of the coated portion of the adhesive material and the spacing between the coated portions (the line width of the uncoated portions). For example, in an area where the adhesive material is applied in a striped pattern as shown in FIG. 6, where the line width of the coated portion of the adhesive material is l and the spacing between the coated portions (the line width of the uncoated portions) is s, the coverage rate of the adhesive material can be calculated using the following formula (2). Adhesive material coverage rate = {l / (l+s)} × 100(%) (2)

[0051] The adhesive material coating weight in the area S where the adhesive material is densely applied is 0.02 g / m 2 It is preferable that the content is 0.8 g / m or more. 2 It is preferable that the content is 0.35 g / m or less. 2 It is more preferable that the adhesive material be applied in a densely coated region S with a basis weight of the adhesive material equal to or greater than the lower limit. If the adhesive material is applied in a densely coated region S with a basis weight of the adhesive material equal to or less than the upper limit, the adhesive strength between the electrodes and the separator can be sufficiently ensured. If the adhesive material is applied in a densely coated region S with a basis weight of the adhesive material equal to or less than the upper limit, the output characteristics of the secondary battery can be sufficiently high.

[0052] Furthermore, the basis weight of the adhesive material in the region T where the adhesive material is sparsely applied is 0.02 g / m 2 It is preferable that the content is 0.03 g / m or more. 2 More preferably, it is 0.35 g / m or more. 2 It is preferable that the adhesive material be applied in a sparsely applied region T with a basis weight of the adhesive material equal to or greater than the lower limit. If the adhesive material is applied in a sparsely applied region T with a basis weight of the adhesive material equal to or less than the upper limit, the adhesive strength between the electrode and the separator can be sufficiently ensured. If the adhesive material is applied in a sparsely applied region T with a basis weight of the adhesive material equal to or less than the upper limit, the output characteristics of the secondary battery can be sufficiently high. In this specification, when an adhesive composition containing an adhesive material and a solvent is supplied to a bonding surface, the "adhesive material" in the "basis weight of adhesive material" refers to the adhesive layer composition in a state in which the solvent has been removed by drying or the like.

[0053] In addition, in each of the above-mentioned "area S where the adhesive material is densely applied" and "area T where the adhesive material is sparsely applied," the adhesive material may be arranged (applied) in the same pattern throughout, or adhesive materials arranged (applied) in multiple different patterns may be mixed.

[0054] In each region, the pattern in which the adhesive material is applied may gradually change along a certain direction. For example, when the adhesive material is applied in a dot pattern, the radius and center-to-center distance of the dots of the adhesive material may gradually change along a certain direction, and when the adhesive material is applied in a stripe pattern, the line width of the coated portion of the adhesive material and the interval between the coated portions (line width of the uncoated portion) may gradually change along a certain direction.

[0055] Here, the direction in which the pattern in which the adhesive material is applied gradually changes is not particularly limited as long as the desired effects of the present invention can be obtained. For example, in at least one of the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied", it is preferable that the pattern in which the adhesive material is applied gradually changes along the direction from the center of the surface Z to the periphery of the surface Z, so that the coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z to the periphery of the surface Z when viewed as a whole. If the coverage of the adhesive material gradually decreases from the center of the surface Z to the periphery of the surface Z, the cycle characteristics of the secondary battery can be further improved.

[0056] Here, a case in which the coverage rate of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z will be described with reference to the drawings. In the surface Z shown in FIG. 7, there is a region S (coverage rate of adhesive material: G) where the adhesive material is densely applied. In addition, the region T1 (coverage rate of adhesive material: H1) where the adhesive material is sparsely applied, the region T2 (coverage rate of adhesive material: H2) where the adhesive material is more sparsely applied, and the region T3 (coverage rate of adhesive material: H3) where the adhesive material is applied even more sparsely are each present as a part of the region T where the adhesive material is applied sparsely. Here, the coverage rate of the adhesive material in each region satisfies the relational expression: G>H1>H2>H3. The region T3 where the adhesive material is applied even more sparsely is a region inside the periphery of the surface Z and outside the region T2 where the adhesive material is applied even more sparsely. In addition, the region T2 where the adhesive material is applied even more sparsely is a region inside the region T3 where the adhesive material is applied even more sparsely and outside the region T1 where the adhesive material is applied sparsely. Furthermore, the region T1 where the adhesive material is applied sparsely is inside the region T2 where the adhesive material is applied more sparsely, and is outside the region S where the adhesive material is applied densely. Moreover, the region S where the adhesive material is applied densely is inside the region T1 where the adhesive material is applied sparsely. By applying the adhesive material to the surface Z as described above, the coverage rate of the adhesive material on the surface Z can be gradually decreased from the center of the surface Z toward the periphery of the surface Z. 7, the shape of the outer periphery of each of the region S where the adhesive material is densely applied, the region T1 where the adhesive material is sparsely applied, and the region T2 where the adhesive material is more sparsely applied is elliptical, but is not limited thereto, and may be, for example, a shape similar to the shape of the surface Z. In addition, the shape of the outer periphery of each of the above-mentioned regions may have a center at the same position as the center R of the surface Z, or may have a center at a position different from the center R of the surface Z.

[0057] The above-mentioned central region P may or may not coincide with the "region S where the adhesive material is densely applied." Therefore, the central region P may only include a portion corresponding to the "region S where the adhesive material is densely applied," or may include a mixture of a portion corresponding to the "region S where the adhesive material is densely applied" and a portion corresponding to the "region S where the adhesive material is sparsely applied." In addition, the above-mentioned other region Q may or may not coincide with the "region T where the adhesive material is sparsely applied." Therefore, the other region Q may only have a portion corresponding to the "region T where the adhesive material is sparsely applied," or may have a portion corresponding to the "region S where the adhesive material is densely applied" and a portion corresponding to the "region S where the adhesive material is sparsely applied."

[0058] Here, in the case where an area U, which is either the central area P or one of the other areas Q, contains a mixture of an area S where the adhesive material is densely applied and an area T where the adhesive material is sparsely applied, the coverage rate of the adhesive material in the area U can be calculated using the following formula (3). Coverage rate of adhesive material in region U = (coverage rate of adhesive material in region S) × (ratio of area of ​​region S to the total area of ​​region U) + (coverage rate of adhesive material in region T) × (ratio of area of ​​region T to the total area of ​​region U) (3)

[0059] It is preferable that the coverage rate E of the adhesive material in the central region P is greater than the coverage rate F of the adhesive material in the other regions Q. Specifically, the coverage E of the adhesive material in the central region P is preferably 1.1% or more, more preferably 1.4% or more, even more preferably 3% or more, and preferably 30% or less, more preferably 10% or less, and even more preferably 8% or less. If the coverage E of the adhesive material in the central region P is equal to or greater than the lower limit, the cycle characteristics of the secondary battery can be further improved. On the other hand, if the coverage E of the adhesive material in the central region P is equal to or less than the upper limit, the output characteristics of the secondary battery can be ensured to be sufficiently high.

[0060] Moreover, it is preferable that the coverage rate F of the adhesive material in the other regions Q is smaller than the coverage rate E of the adhesive material in the central region P. Specifically, the coverage F of the adhesive material in the other regions Q is preferably 0.3% or more, more preferably 0.5% or more, and preferably less than 0.4×E%. If the coverage F of the adhesive material in the other regions Q is equal to or greater than the lower limit, the adhesive strength between the electrode and the separator can be sufficiently ensured. On the other hand, if the coverage F of the adhesive material in the other regions Q is less than the upper limit, the cycle characteristics of the secondary battery can be further improved.

[0061] Furthermore, the ratio (E / F) of the coverage rate E of the adhesive material in the central region P to the coverage rate F of the adhesive material in the other regions Q is preferably 1.6 or more, more preferably 2.0 or more, and even more preferably 2.6 or more, and is preferably 16.0 or less, more preferably 10.0 or less, and even more preferably 8.0 or less. If the ratio (E / F) of the coverage rate E of the adhesive material in the central region P to the coverage rate F of the adhesive material in the other regions Q is equal to or greater than the above lower limit, the cycle characteristics of the secondary battery can be further improved. On the other hand, if the ratio (E / F) of the coverage rate E of the adhesive material in the central region P to the coverage rate F of the adhesive material in the other regions Q is equal to or less than the above upper limit, both the adhesive force between the electrode and the separator and the output characteristics of the secondary battery can be achieved at a high level.

[0062] The weight of the adhesive material in the central region P is 0.02 g / m 2 It is preferable that the content is 0.8 g / m or more. 2 It is preferable that the content is 0.35 g / m or less. 2 It is more preferable that the adhesive material in the central region P is equal to or less than the lower limit. If the adhesive material weight in the central region P is equal to or more than the lower limit, the adhesive strength between the electrode and the separator can be sufficiently ensured. Also, if the adhesive material weight in the central region P is equal to or less than the upper limit, the output characteristics of the secondary battery can be sufficiently high.

[0063] Furthermore, the basis weight of the adhesive material in the other region Q is 0.02 g / m 2 It is preferable that the content is 0.03 g / m or more. 2More preferably, it is 0.35 g / m or more. 2 It is preferable that the adhesive material in the other region Q has a weight per unit area of ​​the adhesive material not less than the above lower limit. If the weight per unit area of ​​the adhesive material in the other region Q is not less than the above upper limit, the adhesive strength between the electrode and the separator can be sufficiently ensured. Also, if the weight per unit area of ​​the adhesive material in the other region Q is not more than the above upper limit, the output characteristics of the secondary battery can be sufficiently high.

[0064] -Details of adhesive materials- Here, the adhesive material is not particularly limited as long as it does not inhibit the battery reaction, and any adhesive material used in the field of secondary batteries can be used. Among them, it is preferable to use an adhesive material made of a polymer as the adhesive material. The polymer constituting the adhesive material may be only one type, or may be two or more types.

[0065] Polymers that can be used as adhesive materials are not particularly limited, and examples thereof include fluoropolymers such as polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP); conjugated diene polymers such as styrene-butadiene copolymer (SBR) and acrylonitrile-butadiene copolymer (NBR); hydrogenated conjugated diene polymers; polymers containing (meth)acrylic acid alkyl ester monomer units (acrylic polymers); and polyvinyl alcohol polymers such as polyvinyl alcohol (PVA). In the present invention, the term "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0066] The shape of the adhesive material made of a polymer is not particularly limited, and may be particulate, non-particulate, or a combination of particulate and non-particulate. In addition, when the adhesive material made of a polymer is a particulate polymer, the particulate polymer adhesive material may be particles having a single phase structure formed from a single polymer, or particles having a heterogeneous phase structure formed by physically or chemically bonding two or more different polymers. Specific examples of heterogeneous phase structures include a core-shell structure in which the central portion (core portion) and the outer shell portion (shell portion) of a spherical particle are formed from different polymers; and a side-by-side structure in which two or more polymers are arranged side by side. In the present invention, the "core-shell structure" includes not only a structure in which the shell portion completely covers the outer surface of the core portion, but also a structure in which the shell portion partially covers the outer surface of the core portion, as shown in Figure 8. In the present invention, even if the outer surface of the core part appears to be completely covered by the shell part, if a hole communicating between the inside and outside of the shell part is formed, the shell part is considered to be a shell part partially covering the outer surface of the core part. Therefore, for example, a particulate polymer having a shell part having a pore communicating from the outer surface of the shell part (i.e., the peripheral surface of the particulate polymer) to the outer surface of the core part corresponds to a particulate polymer in which the shell part partially covers the outer surface of the core part.

[0067] The electrolyte of the adhesive material (volume ratio: ethylene carbonate / diethyl carbonate = 3 / 7 mixed solvent) was 1 mol / L of LiPF 6 The degree of swelling of the adhesive material with respect to a solution in which the electrolyte is dissolved (hereinafter, sometimes simply referred to as "degree of swelling") is preferably 110% or more, and is preferably 1500% or less, more preferably 1300% or less, and particularly preferably 1000% or less. When the degree of swelling of the adhesive material is equal to or less than the upper limit, the permeability of the electrolyte to the center of the positive electrode or negative electrode can be improved. The degree of swelling of the adhesive material with respect to the electrolyte can be measured by the method described in the examples of this specification.

[0068] --Particulate polymer-- As the adhesive material, a particulate polymer is preferably used. As the particulate polymer, either a particulate polymer having a core-shell structure or a particulate polymer not having a core-shell structure may be used, but it is preferable to use at least a particulate polymer having a core-shell structure, and it is more preferable to use a particulate polymer having a core-shell structure and a particulate polymer not having a core-shell structure in combination. In addition, when a particulate polymer having a core-shell structure and a particulate polymer not having a core-shell structure are used in combination, the mass ratio of the particulate polymer having a core-shell structure to the particulate polymer having a core-shell structure in the adhesive material can be appropriately adjusted within a range in which the desired effects of the present invention can be obtained.

[0069] =Particulate polymer having a core-shell structure= The particulate polymer having a core-shell structure is a component that functions as a binder in an adhesive material that bonds battery components such as separators, electrodes, etc. By using the particulate polymer having a core-shell structure as a binder, the battery components can be firmly bonded to each other via the adhesive material, and the secondary battery can exhibit excellent output characteristics.

[0070] Here, the particulate polymer has a core-shell structure comprising a core and a shell covering the outer surface of the core. Here, the shell may cover the entire outer surface of the core, or may cover only a part of the outer surface of the core. Even if the outer surface of the core appears to be completely covered by the shell, the shell is a shell that partially covers the outer surface of the core as long as a hole that communicates between the inside and outside of the shell is formed.

[0071] A cross-sectional structure of an example of the particulate polymer is shown in FIG. 8. In FIG. 8, the particulate polymer 300 has a core-shell structure including a core portion 310 and a shell portion 320. Here, the core portion 310 is a portion of the particulate polymer 300 that is located inside the shell portion 320. The shell portion 320 is a portion that covers the outer surface 310S of the core portion 310, and is usually the outermost portion of the particulate polymer 300. In the example of FIG. 8, the shell portion 320 does not cover the entire outer surface 310S of the core portion 310, but only partially covers the outer surface 310S of the core portion 310.

[0072] In addition, the particulate polymer may have any other constituent element other than the above-mentioned core part and shell part, so long as the intended effect is not significantly impaired. Specifically, for example, the particulate polymer may have a part formed of a polymer other than the core part inside the core part. As a specific example, the seed particles used when producing the particulate polymer by the seed polymerization method may remain inside the core part. However, from the viewpoint of significantly exhibiting the intended effect, it is preferable that the particulate polymer has only the core part and the shell part.

[0073] The glass transition temperature of the polymer in the core portion of the particulate polymer is preferably -30°C or higher, more preferably -20°C or higher, preferably 200°C or lower, more preferably 100°C or lower, and particularly preferably 50°C or lower. If the glass transition temperature of the polymer in the core portion is -30°C or higher, the battery components can be bonded more firmly via the adhesive material. On the other hand, if the glass transition temperature of the polymer in the core portion is 200°C or lower, the polymerization stability of the particulate polymer can be ensured. The glass transition temperature of the polymer can be measured by the method described in the Examples section of this specification. The glass transition temperature of the core polymer can be adjusted, for example, by changing the types and ratio of monomers used in preparing the core polymer.

[0074] Examples of monomers used to prepare the core polymer include vinyl chloride monomers such as vinyl chloride and vinylidene chloride; vinyl acetate monomers such as vinyl acetate; aromatic vinyl monomers such as styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene; vinylamine monomers such as vinylamine; vinylamide monomers such as N-vinylformamide and N-vinylacetamide; methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl meth ... Examples of the monomers include (meth)acrylic acid ester monomers such as perfluorohexyl methacrylate, ethyl methacrylate, butyl methacrylate, and cyclohexyl methacrylate; (meth)acrylamide monomers such as acrylamide and methacrylamide; (meth)acrylonitrile monomers such as acrylonitrile and methacrylonitrile; fluorine-containing (meth)acrylic acid ester monomers such as 2-(perfluorohexyl)ethyl methacrylate and 2-(perfluorobutyl)ethyl acrylate; maleimide; and maleimide derivatives such as phenylmaleimide. These may be used alone or in combination of two or more at any ratio. In the present invention, (meth)acrylic means acrylic and / or methacrylic, and (meth)acrylonitrile means acrylonitrile and / or methacrylonitrile.

[0075] Among these monomers, from the viewpoint of further strongly bonding the battery components to each other via the adhesive material, it is preferable to use at least a (meth)acrylic acid ester monomer as the monomer used for preparing the core polymer, and it is more preferable to use a combination of a (meth)acrylic acid ester monomer and an aromatic vinyl monomer, or a combination of a (meth)acrylic acid ester monomer and a (meth)acrylonitrile monomer, and it is particularly preferable to use a combination of a (meth)acrylic acid ester monomer and an aromatic vinyl monomer. That is, it is preferable that the core polymer contains at least a (meth)acrylic acid ester monomer unit, it is more preferable that it contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit or a (meth)acrylonitrile monomer unit, and it is even more preferable that it contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit. In the present invention, "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer". In the present invention, the term "(meth)acrylic acid ester monomer" refers to a monofunctional (meth)acrylic acid ester monomer having only one polymerization reactive group.

[0076] From the viewpoint of further firmly bonding the battery components together via the adhesive material, the proportion of the (meth)acrylic acid ester monomer units in the core polymer is preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 20% by mass or more, with the total repeating units (total monomer units) contained in the core polymer being 100% by mass, and is preferably 80% by mass or less, and more preferably 70% by mass or less. Furthermore, when the core polymer contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit, the proportion of the aromatic vinyl monomer units in the core polymer is, from the viewpoint of further firmly bonding the battery components together via the adhesive material, preferably 15% by mass or more, more preferably 20% by mass or more, and particularly preferably 25% by mass or more, with all repeating units (all monomer units) contained in the core polymer being 100% by mass, preferably 95% by mass or less, more preferably 80% by mass or less, and particularly preferably 65% ​​by mass or less. Furthermore, when the core polymer contains (meth)acrylic acid ester monomer units and (meth)acrylonitrile monomer units, the proportion of (meth)acrylonitrile monomer units in the core polymer is, from the viewpoint of further firmly bonding the battery components together via the adhesive material, preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 15% by mass or more, with the total repeating units (total monomer units) contained in the core polymer being 100% by mass, preferably 30% by mass or less, and more preferably 25% by mass or less.

[0077] The core polymer may contain an acid group-containing monomer unit. Examples of the acid group-containing monomer include a monomer having an acid group, such as a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, or a monomer having a phosphoric acid group.

[0078] Examples of the monomer having a carboxylic acid group include monocarboxylic acid and dicarboxylic acid. Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid. Examples of the dicarboxylic acid include maleic acid, fumaric acid, and itaconic acid. Examples of monomers having a sulfonic acid group include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid. Furthermore, examples of monomers having a phosphate group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In the present invention, (meth)allyl means allyl and / or methallyl, and (meth)acryloyl means acryloyl and / or methacryloyl. Among these, as the acid group-containing monomer, a monomer having a carboxylic acid group is preferable, among which a monocarboxylic acid is preferable, and (meth)acrylic acid is more preferable. The acid group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0079] The proportion of the acid group-containing unit in the core polymer is preferably 0.1% by mass or more, more preferably 1% by mass or more, and preferably 15% by mass or less, and more preferably 10% by mass or less, based on 100% by mass of all repeating units (all monomer units) contained in the core polymer. By keeping the proportion of the acid group-containing unit within the above range, the dispersibility of the core polymer can be increased during preparation of the particulate polymer, and a shell portion that partially covers the outer surface of the core polymer can be easily formed.

[0080] In addition to the above monomer units, the core polymer preferably contains a crosslinkable monomer unit. The crosslinkable monomer is a monomer that can form a crosslinked structure during or after polymerization by heating or irradiation with energy rays.

[0081] Examples of the crosslinkable monomer include polyfunctional monomers having two or more polymerization reactive groups in the monomer. Examples of such polyfunctional monomers include divinyl monomers such as divinylbenzene, 1,3-butadiene, isoprene, and allyl methacrylate; di(meth)acrylic acid ester monomers such as ethylene dimethacrylate, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, and 1,3-butylene glycol diacrylate; tri(meth)acrylic acid ester monomers such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate; and γ-methacryloxypropyltrimethoxysilane. Among these, di(meth)acrylic acid ester monomers are more preferred. In addition, these may be used alone or in combination of two or more at any ratio.

[0082] The proportion of the crosslinkable monomer units in the core polymer is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and particularly preferably 0.4% by mass or more, and is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 3% by mass or less, based on 100% by mass of all repeating units (all monomer units) contained in the core polymer. By keeping the proportion of the crosslinkable monomer units within the above range, the battery components can be bonded together more firmly via the adhesive material.

[0083] The glass transition temperature of the polymer of the shell part of the particulate polymer is preferably 70° C. or higher, more preferably 80° C. or higher, particularly preferably 90° C. or higher, and preferably 140° C. or lower, more preferably 130° C. or lower, particularly preferably 120° C. or lower. If the glass transition temperature of the polymer of the shell part is 70° C. or higher, the output characteristics of the secondary battery can be improved. On the other hand, if the glass transition temperature of the polymer of the shell part is 140° C. or lower, the battery components can be bonded more firmly to each other via the adhesive material. The glass transition temperature of the shell polymer can be adjusted, for example, by changing the types and ratio of monomers used in preparing the shell polymer.

[0084] The glass transition temperature of the polymer in the shell portion is preferably at least 30°C higher, and more preferably at least 50°C higher, than the glass transition temperature of the polymer in the core portion described above, from the viewpoint of maintaining the shape of the particulate polymer after bonding of the battery components and suppressing an increase in resistance.

[0085] Examples of monomers used to prepare the polymer of the shell portion include the same monomers as those exemplified as monomers that can be used to produce the polymer of the core portion. Moreover, such monomers may be used alone or in combination of two or more kinds in any ratio.

[0086] Among these monomers, it is preferable to use an aromatic vinyl monomer as the monomer used for preparing the shell polymer from the viewpoint of further strongly bonding the battery components together via the adhesive material, i.e., the shell polymer preferably contains an aromatic vinyl monomer unit.

[0087] From the viewpoint of bonding battery components together more firmly via the adhesive material, the proportion of aromatic vinyl monomer units in the polymer of the shell portion is preferably 85% by mass or more, more preferably 90% by mass or more, particularly preferably 95% by mass or more, and preferably 99% by mass or less, with all repeating units (all monomer units) contained in the polymer of the shell portion being 100% by mass.

[0088] The polymer of the shell part may contain an acid group-containing monomer unit in addition to the aromatic vinyl monomer unit. Here, the acid group-containing monomer may be a monomer having an acid group, such as a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, or a monomer having a phosphoric acid group. Specifically, the acid group-containing monomer may be the same monomer as the acid group-containing monomer that can be used to form the core part. Among these, as the acid group-containing monomer, a monomer having a carboxylic acid group is preferable, among which a monocarboxylic acid is more preferable, and (meth)acrylic acid is further preferable. The acid group-containing monomer may be used alone or in combination of two or more kinds in any ratio.

[0089] The proportion of the acid group-containing monomer units in the polymer of the shell portion is preferably 0.1% by mass or more, more preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on 100% by mass of all repeating units (all monomer units) contained in the polymer of the shell portion. By keeping the proportion of the acid group-containing monomer units within the above range, the dispersibility of the particulate polymer can be improved, and the battery components can be bonded together even more firmly via the adhesive material.

[0090] In the particulate polymer having a core-shell structure, the mass ratio of the core polymer to the shell polymer (core / shell) is preferably 5 / 5 or more, more preferably 6 / 4 or more, and preferably 9 / 1 or less, and more preferably 8 / 2 or less. When the mass ratio of the core polymer to the shell polymer (core / shell) is within the above-mentioned range, the battery components can be bonded together more firmly via the adhesive material.

[0091] The volume average particle diameter of the particulate polymer having a core-shell structure is preferably 100 nm or more, more preferably 300 nm or more, and is preferably 1000 nm or less, more preferably 900 nm or less, even more preferably 800 nm or less, and even more preferably 700 nm or less. If the volume average particle diameter of the particulate polymer having a core-shell structure is within the above-mentioned range, the battery components can be bonded more firmly to each other via the adhesive material. The volume average particle size of the particulate polymer can be measured by the method described in the Examples of this specification.

[0092] The particulate polymer having the above-mentioned core-shell structure can be prepared, for example, by using the monomer of the core polymer and the monomer of the shell polymer, and polymerizing them stepwise while changing the ratio of the monomers over time.Specifically, the particulate polymer can be prepared by a continuous multi-stage emulsion polymerization method and a multi-stage suspension polymerization method in which the polymer of the previous stage is successively covered with the polymer of the later stage.

[0093] An example of the method for obtaining a particulate polymer having the above-mentioned core-shell structure by a multi-stage emulsion polymerization method will be described below.

[0094] In the polymerization, an anionic surfactant such as sodium dodecylbenzenesulfonate or sodium dodecylsulfate, a nonionic surfactant such as polyoxyethylene nonylphenyl ether or sorbitan monolaurate, or a cationic surfactant such as octadecylamine acetate can be used as an emulsifier in accordance with a conventional method. In addition, a peroxide such as t-butylperoxy-2-ethylhexanoate, potassium persulfate, or cumene peroxide, or an azo compound such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) or 2,2'-azobis(2-amidinopropane) hydrochloride can be used as a polymerization initiator.

[0095] The polymerization procedure is as follows: first, a monomer for forming the core part and an emulsifier are mixed and emulsion-polymerized all at once to obtain a particulate polymer for forming the core part. Then, a monomer for forming the shell part is polymerized in the presence of the particulate polymer for forming the core part, thereby obtaining a particulate polymer having the above-mentioned core-shell structure.

[0096] In this case, when preparing a particulate polymer in which the outer surface of the core part is partially covered with the shell part, it is preferable to feed the monomer forming the polymer of the shell part to the polymerization system in a divided manner or continuously. By feeding the monomer forming the polymer of the shell part to the polymerization system in a divided manner or continuously, the polymer constituting the shell part is formed in a particulate form, and this particle is bonded to the core part to form the shell part partially covering the core part.

[0097] =Particulate polymer having no core-shell structure= The adhesive material may contain a particulate polymer not having a core-shell structure in addition to the particulate polymer having the core-shell structure described above.

[0098] Here, the glass transition temperature of the particulate polymer having no core-shell structure is preferably -40°C or higher, more preferably -35°C or higher, even more preferably -30°C or higher, preferably 0°C or lower, more preferably -10°C or lower, and even more preferably -20°C or lower. If the glass transition temperature of the particulate polymer having no core-shell structure is -40°C or higher, the battery components can be bonded more firmly via the adhesive material. On the other hand, if the glass transition temperature of the particulate polymer having no core-shell structure is 0°C or lower, the polymerization stability of the particulate polymer can be ensured.

[0099] The monomer used to prepare the particulate polymer without a core-shell structure may be the same as the monomer exemplified as the monomer that can be used to prepare the core polymer of the particulate polymer with a core-shell structure.For example, the monomer used to prepare the particulate polymer without a core-shell structure is preferably a (meth)acrylic acid ester monomer, an aromatic vinyl monomer, an acid group-containing monomer, and a crosslinkable monomer.In addition, such a monomer may be used alone or in combination of two or more kinds at any ratio.

[0100] From the viewpoint of more firmly bonding battery components together via an adhesive material, the proportion of (meth)acrylic acid ester monomer units in a particulate polymer not having a core-shell structure is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, and is preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, with all repeating units (total monomer units) contained in the polymer being 100% by mass.

[0101] From the viewpoint of more firmly bonding battery components together via an adhesive material, the proportion of aromatic vinyl monomer units in a particulate polymer not having a core-shell structure is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, with all repeating units (total monomer units) contained in the polymer being 100% by mass, preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less.

[0102] The proportion of the acid group-containing monomer unit in the particulate polymer having no core-shell structure is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 5% by mass or less, based on the total repeating units (total monomer units) contained in the polymer being 100% by mass. By keeping the proportion of the acid group-containing monomer unit in the particulate polymer having no core-shell structure within the above range, the dispersibility of the particulate polymer can be improved.

[0103] From the viewpoint of more firmly bonding battery components together via an adhesive material, the proportion of crosslinkable monomer units in a particulate polymer not having a core-shell structure is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, with the total repeating units (total monomer units) contained in the polymer being 100% by mass, preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0104] The volume average particle diameter of the particulate polymer having no core-shell structure is preferably 50 nm or more, more preferably 100 nm or more, and preferably 600 nm or less. If the volume average particle diameter of the particulate polymer having no core-shell structure is within the above-mentioned range, the battery components can be bonded more firmly to each other via the adhesive material.

[0105] The particulate polymer without core-shell structure is not particularly limited, and can be prepared, for example, by polymerizing the monomer composition containing the above-mentioned monomer in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is usually the same as the ratio of each monomer unit in the particulate polymer without core-shell structure. And, the polymerization method and polymerization reaction are not particularly limited, and can be used known polymerization method and polymerization reaction.

[0106] -others- The adhesive material present in the central region P and the adhesive material present in the other regions Q may be the same or different. Therefore, the above-mentioned "area S where the adhesive material is densely applied" and "area T where the adhesive material is sparsely applied" may be applied with the same adhesive material or different adhesive materials.

[0107] In the above-mentioned section "Method of applying adhesive material", the case where the adhesive material is applied so that there are "areas S where the adhesive material is applied densely" and "areas T where the adhesive material is applied sparsely" on the surface Z has been described, but the laminate in the secondary battery of the present invention is not limited to this, and the adhesive material can also be applied so that there is a "coated area S1" instead of the "area S where the adhesive material is applied densely" and a "coated area S2" instead of the "area T where the adhesive material is applied sparsely". That is, the adhesive material can also be applied so that there are a "coated area S1" and a "coated area S2" on the surface Z.

[0108] Here, the coverage rate and / or basis weight of the adhesive material in each of the "coated area S1" and "coated area S2" can be set within the same range as the preferred range of the coverage rate and / or basis weight of the adhesive material in the above-mentioned "area S where the adhesive material is densely coated." The adhesive material may be coated so that the coverage rate and / or basis weight of the adhesive material are the same in the "coated area S1" and the "coated area S2."

[0109] The adhesive material applied to the "coating area S1" is different from the adhesive material applied to the "coating area S2". By appropriately selecting and using different adhesive materials as the adhesive material applied to the "coating area S1" and the adhesive material applied to the "coating area S2", the resistance A per unit area of ​​the central area P can be made larger than the resistance B per unit area of ​​the other areas Q.

[0110] For example, a particulate polymer M1 and a particulate polymer M2 having different swelling degrees can be used for the adhesive material to be applied to the "coating region S1" and the adhesive material to be applied to the "coating region S2".

[0111] Here, the electrolyte of the particulate polymer M1 contained in the adhesive material to be applied to the "coating area S1" (volume ratio: ethylene carbonate / diethyl carbonate = 3 / 7 mixed solvent) is LiPF at a concentration of 1 mol / L. 6 The degree of swelling in the aqueous solution in which the polymer is dissolved is preferably 800% or more, more preferably 1000% or more, and is preferably 1300% or less. In addition, the electrolyte of the particulate polymer M2 contained in the adhesive material to be applied to the "coating area S2" (volume ratio: ethylene carbonate / diethyl carbonate = 3 / 7 mixed solvent) is 1 mol / L of LiPF 6 The degree of swelling in the liquid in which the polymer is dissolved is preferably 110% or more, and more preferably less than 800%, more preferably 500% or less, and even more preferably 300% or less. By setting the swelling degree of the particulate polymers M1 and M2 within the above-mentioned predetermined range, the resistance A per unit area of ​​the central region P can be made larger than the resistance B per unit area of ​​the other regions Q.

[0112] As the particulate polymers M1 and M2, for example, particulate polymers having a core-shell structure as described above in the section "Details of adhesive material" can be used. Among the particulate polymers having the core-shell structure described above, the particulate polymer M1 is preferably one in which the core polymer contains a (meth)acrylic acid ester monomer unit and a (meth)acrylonitrile monomer unit, and the particulate polymer M2 is preferably one in which the core polymer contains a (meth)acrylic acid ester monomer unit and an aromatic vinyl monomer unit.

[0113] Also, for example, particulate polymers having different structures may be used in the adhesive material applied to the "coating region S1" and the adhesive material applied to the "coating region S2". More specifically, a particulate polymer having a core-shell structure may be used as the particulate polymer M3 contained in the adhesive material applied to the "coating region S1", and a particulate polymer not having a core-shell structure may be used as the particulate polymer M4 contained in the adhesive material applied to the "coating region S2". Here, for example, the particulate polymer M3 may be a particulate polymer having a core-shell structure as described above in the section "Details of the adhesive material". Also, for example, the particulate polymer M4 may be a particulate polymer consisting of only a polymer having the same composition as the polymer of the core part in the particulate polymer having a core-shell structure as described above in the section "Details of the adhesive material".

[0114] <<Laminate manufacturing method>> The method for producing the laminate in the secondary battery of the present invention includes a step (A) of preparing a laminate, and a step (B) of cutting the laminate, and optionally, when the laminate prepared in the step (A) does not include a positive electrode, further includes a step (C) of laminating a positive electrode to the cut piece obtained by cutting the laminate in the step (B).

[0115] [Process (A)] Here, examples of the laminate prepared in the step (A) include the following (I) and (II). (I) A laminate comprising a long negative electrode raw material or negative electrode (hereinafter, the "negative electrode raw material or negative electrode" may be referred to as the "negative electrode material"), a long first separator raw material laminated to one surface of the negative electrode material, and a long second separator raw material laminated to the other surface of the negative electrode material, and optionally a positive electrode laminated to the surface of the first separator raw material opposite to the negative electrode material side (hereinafter, may be referred to as the "laminated body (I)"). (II) A laminate obtained by laminating a negative electrode material consisting of a long negative electrode raw material, a long first separator raw material, a positive electrode, and a long second separator raw material in this order (hereinafter, sometimes referred to as "laminate (II)").

[0116] In the method for producing a laminate in a secondary battery of the present invention, when a laminate (I) is prepared in step (A), a laminate is usually obtained that includes a negative electrode, a first separator bonded to one surface of the negative electrode, a positive electrode bonded to the surface of the first separator opposite to the negative electrode, and a second separator bonded to the other surface of the negative electrode, as shown in FIG. 1, for example. In addition, when the above-mentioned laminate (I) does not have a positive electrode, in the method for producing a laminate in the secondary battery of the present invention, usually, the laminate is produced by carrying out the step (C) after the step (B). In the method for producing a laminate in a secondary battery of the present invention, when a laminate (II) is prepared in step (A), a laminate is usually obtained that includes a negative electrode, a first separator bonded to one surface of the negative electrode, a positive electrode bonded to the surface of the first separator opposite the negative electrode side, and a second separator bonded to the surface of the positive electrode opposite the first separator side, as shown in FIG. 3, for example.

[0117] Here, the preparation of the laminate in step (A) is usually performed by applying an adhesive material to the bonding surfaces of the members to be bonded to each other and bonding the members constituting the laminate together via the adhesive material. That is, step (A) includes step (a1) of applying an adhesive material to bonding surface Y between the negative electrode material and the separator raw material to be bonded to the negative electrode material, and may further include step (a2) of applying an adhesive material to bonding surface X between the separator raw material and the positive electrode.

[0118] The "separator raw roll to be laminated to the negative electrode material" refers to the first separator raw roll and the second separator raw roll when the laminate to be prepared is the laminate (I), and refers to the first separator raw roll when the laminate is the laminate (II). The adhesive material may be applied to only one of the members, or to both of the members to be laminated to each other.

[0119] Specifically, in the step (A), for example, a laminate (I) can be prepared as shown in FIG.

[0120] Here, in FIG. 9, a long first separator roll 10A unwound from a first separator roll is bonded to one surface of a negative electrode material made of a long negative electrode roll 20A unwound from a negative electrode roll via an adhesive material supplied from a coating machine 51, and a long second separator roll 30A unwound from a second separator roll is bonded to the other surface of the negative electrode material made of the negative electrode roll 20A via an adhesive material supplied from a coating machine 52. The bonding can be performed, for example, using pressure rollers 61 and 62. Then, a positive electrode 40 is bonded to the surface of the first separator roll 10A opposite to the negative electrode roll 20A via an adhesive material supplied from a coating machine 53 at a predetermined arrangement pitch to obtain a bonded body (I) having a positive electrode. In FIG. 9 , an adhesive material is supplied from a coater 54 to the surface of the second separator raw material 30A opposite to the negative electrode raw material 20A side, so that the laminates obtained by cutting the laminate between longitudinally adjacent positive electrodes 40 can be stacked to produce a laminate, thereby enabling the laminates to be well bonded to each other.

[0121] FIG. 10 is an explanatory diagram showing an example of the coater (nozzle head) in FIG. In FIG. 10, droplets 50 of adhesive material are applied onto a substrate 60 through nozzles 55 of coaters 51-54.

[0122] The method for preparing the laminate in step (A) is not limited to the above-mentioned example. For example, in FIG. 9, after cutting the laminate, adhesive material may be supplied from a coater 54 to the obtained cut pieces.

[0123] -Anode materials and cathode- Here, the electrode (negative electrode or positive electrode) is not particularly limited, and for example, an electrode obtained by cutting a long electrode original (negative electrode original or positive electrode original) can be used. The electrode original (negative electrode original or positive electrode original) can be an electrode original made of an electrode base material formed by forming an electrode mixture layer (negative electrode mixture layer or positive electrode mixture layer) on one side or both sides of a long current collector, or an electrode original made by further forming a porous membrane layer on the electrode mixture layer of the electrode base material. The current collector, electrode mixture layer and porous membrane layer are not particularly limited, and any current collector, electrode mixture layer and porous membrane layer that can be used in the field of secondary batteries, such as those described in JP 2013-145763 A, can be used. Here, the porous membrane layer refers to a layer containing non-conductive particles, such as those described in JP 2013-145763 A.

[0124] -Separator roll- The separator raw material is not particularly limited, and for example, a separator raw material made of a long separator substrate, or a separator raw material made of a long separator substrate having a porous membrane layer formed on one or both sides thereof can be used. The separator substrate and the porous membrane layer are not particularly limited, and any separator substrate and porous membrane layer that can be used in the field of secondary batteries, such as those described in JP-A-2012-204303 and JP-A-2013-145763, can be used.

[0125] In the step (a1) of applying an adhesive material to the lamination surface Y of the separator raw material to be laminated to the negative electrode material, or in the step (a2) of applying an adhesive material to the lamination surface X of the separator raw material to be laminated to the positive electrode, it is preferable to apply the adhesive material to the lamination surface Z, which is at least one of the lamination surfaces X and Y, such that the coverage E of the adhesive material in a central region P having a center at the same position as the center R of the surface Z, a shape similar to the shape of the surface Z, and an area of ​​10% of the area of ​​the surface Z is greater than the coverage F of the adhesive material in the other regions Q of the surface Z other than the central region P. This can further improve the cycle characteristics of the secondary battery. As a method for applying the adhesive material to the surface Z so that the coverage rate E of the adhesive material in the central region P is greater than the coverage rate F of the adhesive material in the other regions Q, for example, the adhesive material application method described above in the section "Surface Z, central region P, other regions Q" can be used. The coverage rate E of the adhesive material in the central region P, the coverage rate F of the adhesive material in the other regions Q, and the range of the value of the ratio (E / F) of the coverage rate E to the coverage rate F can also be set within the preferred ranges described above in the same section.

[0126] In the step (a2), an adhesive material is applied to the bonding surface between the separator sheet and the positive electrode. Specifically, in the case of preparing a laminate including a positive electrode in step (A) (e.g., FIG. 9), and in the case of preparing a laminate (a laminate without a positive electrode) in which an adhesive material is applied in advance to the position where the positive electrode will be attached after cutting, the adhesive material is applied to the bonding surface between the separator roll and the positive electrode in step (a2). That is, for example, in FIG. 9, an adhesive material is applied from a coater 53 to the bonding surface between the first separator roll 10A and the positive electrode 40.

[0127] In step (A), for example, as shown in FIG. 9, an adhesive material may be supplied to one surface of the laminate (in FIG. 9, the surface of the second separator raw material 30A opposite to the negative electrode raw material 20A) so that the laminates can be well bonded to each other when they are stacked to produce a laminate.

[0128] [Process (B)] In step (B), the bonded body is cut using a cutter 70. When the bonded body having a positive electrode is cut in step (B), the cut body obtained becomes a laminate. Here, the cutter 70 can be any cutter that can be used in the field of secondary battery manufacturing, such as a cutter that clamps and cuts the bonded body with cutting blades from both sides in the thickness direction of the bonded body.

[0129] Then, in the step (B) carried out after the step (A), as described above, the laminate can be cut satisfactorily while preventing the separator from coming off the negative electrode.

[0130] [Process (C)] In step (C), which can be optionally performed, when the laminate not having a positive electrode is cut in step (B), a positive electrode is attached to the cut piece obtained by cutting the laminate in step (B) to obtain a laminate.

[0131] <Electrolyte> As the electrolyte, an organic electrolyte solution in which a supporting electrolyte is dissolved in an organic solvent is usually used. For example, when the secondary battery is a lithium ion secondary battery, a lithium salt can be used as the supporting electrolyte. For example, LiPF 6 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlCl 4 , LiClO 4 , C.F. 3 SO 3 Li, C. 4 F 9 SO 3 Li, C.F. 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 )NLi, etc. Among these, LiPF is the most popular because it is easily soluble in solvents and has a high degree of dissociation. 6 , LiClO 4 , C.F. 3 SO 3 Li is preferred, and LiPF 6 is particularly preferred. The electrolyte may be used alone or in any combination of two or more kinds in any ratio. Usually, the lithium ion conductivity tends to increase as the supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0132] The organic solvent used in the electrolytic solution is not particularly limited as long as it can dissolve the supporting electrolyte, but for example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), vinylene carbonate (VC), etc.; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and the like are preferably used. A mixture of these solvents may also be used. Among them, it is preferable to use carbonates because they have a high dielectric constant and a wide stable potential range. Generally, the lower the viscosity of the solvent used, the higher the lithium ion conductivity tends to be. Therefore, the lithium ion conductivity can be adjusted by the type of solvent. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. Known additives can be added to the electrolytic solution.

[0133] The secondary battery of the present invention can be manufactured, for example, by stacking the laminated bodies, wrapping or folding the laminated body according to the shape of the battery as necessary, placing the laminated body in a device container (battery container), injecting an electrolyte into the device container, and sealing the device container. The laminated body may be the laminated body itself, or may be manufactured by stacking a plurality of laminated bodies. The laminated body may also be manufactured by stacking the laminated body and additional battery members (electrodes and / or separators, etc.). In addition, the secondary battery of the present invention may be provided with an overcurrent prevention element such as a fuse or a PTC element, an expanded metal, a lead plate, etc., as necessary, in order to prevent an internal pressure rise, overcharging and discharging, etc. The shape of the secondary battery may be any of, for example, a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc.

[0134] (Secondary battery manufacturing method) The method for producing a secondary battery of the present invention is a method for producing a secondary battery having a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order. The method for producing a secondary battery of the present invention is characterized by including a step of applying an adhesive material under predetermined conditions to surface Z, which is at least one of surface X where the positive electrode and the separator are attached and surface Y where the negative electrode and the separator are attached (coating step). According to the method for producing a secondary battery of the present invention, a secondary battery having excellent cycle characteristics can be produced. Moreover, according to the manufacturing method of the present invention, the secondary battery of the present invention described above can be manufactured efficiently. The method for producing a secondary battery of the present invention may include other steps in addition to the above-mentioned coating step.

[0135] <Coating process> In the coating process, the adhesive material is coated onto surface Z such that a coverage rate E of the adhesive material in a central region P having a shape similar to the shape of surface Z, which is at least one of surface X where the positive electrode and separator are bonded and surface Y where the negative electrode and separator are bonded, a center at the same position as the center of surface Z, and an area of ​​10% of the area of ​​surface Z, is greater than a coverage rate F of the adhesive material in other regions Q of surface Z other than central region P. As a method for applying the adhesive material to the surface Z so that the coverage rate E of the adhesive material in the central region P is greater than the coverage rate F of the adhesive material in the other regions Q, for example, the adhesive material application method described above in the "Secondary battery" section can be used. The coverage rate E of the adhesive material in the central region P, the coverage rate F of the adhesive material in the other regions Q, and the range of the ratio of coverage rate E to coverage rate F (E / F) can also be set within the preferred ranges described above in the "Secondary Battery" section. As the positive electrode, separator, negative electrode and adhesive material used in the coating step, those described above in the section "Secondary battery" can be used.

[0136] <Other processes> Examples of the other steps include a lamination step and an assembly step.

[0137] <<Lamination process>> In the lamination step, after the adhesive material is applied to surface Z under the above-mentioned predetermined conditions, the positive electrode, the separator, and the negative electrode are laminated in this order to obtain a laminate. It should be noted that the laminate can also be obtained by carrying out the coating step and lamination step as part of the laminate manufacturing method described above in the "Secondary battery" section.

[0138] <<Assembly process>> The assembly process is a process of assembling a secondary battery using a laminate and an electrolytic solution, for example, a process in which additional battery components (such as electrodes and / or separators) are further laminated as necessary on the laminate obtained by stacking the laminates, and the resulting laminate is then placed in a battery container, and the battery container is injected with the electrolytic solution and sealed to complete the assembly. EXAMPLES

[0139] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In addition, in a polymer produced by copolymerizing multiple types of monomers, the ratio of monomer units formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of that certain monomer to all monomers used in the polymerization of the polymer, unless otherwise specified. In the Production Examples, Examples, and Comparative Examples, the glass transition temperature, the volume average particle size, the swelling degree, the shape of the adhesive material, the basis weight of the coating area, the dry adhesive strength between the electrode and the separator, the cycle characteristics of the secondary battery, the output characteristics, and the temperature difference during discharge were measured and evaluated by the following methods.

[0140] <Glass transition temperature> The aqueous dispersion of the particulate polymer prepared in Production Examples 1 to 6 was dried at 130°C for 1 hour to prepare a sample. 10 mg of the measurement sample was weighed into an aluminum pan, and a differential scanning calorimetry (DSC) curve was obtained by measuring the temperature range of -100°C to 200°C at a heating rate of 10°C / min under the conditions specified in JIS Z8703 using a differential thermal analysis measuring device (SII NanoTechnology's "EXSTAR DSC6220") to obtain a differential scanning calorimetry (DSC) curve. An empty aluminum pan was used as a reference. During this heating process, the intersection point between the baseline immediately before the endothermic peak of the DSC curve where the differential signal (DDSC) is 0.05 mW / min / mg or more appears and the tangent to the DSC curve at the first inflection point that appears after the endothermic peak was determined as the glass transition temperature (°C).

[0141] <Volume average particle size> The volume average particle diameter of the particulate polymer prepared in each production example was measured by a laser diffraction method. Specifically, the aqueous dispersion solution (solid content concentration 0.1 mass%) containing the prepared particles was used as a sample, and the particle size distribution (volume basis) obtained by a laser diffraction type particle size distribution measuring device (manufactured by Beckman Coulter, product name "LS-13 320") was used to obtain the particle diameter at which the cumulative volume calculated from the small diameter side was 50%, which was taken as the volume average particle diameter D50 (nm).

[0142] <Swelling degree> The aqueous dispersion of the particulate polymer prepared in each manufacturing example was dried, and about 0.2 g of the obtained dried material was pressed for 2 minutes under pressing conditions of a temperature of 200°C and a pressure of 5 MPa to obtain a film. The obtained film was cut into a 1 cm square to obtain a test piece, and the mass W2 (g) of this test piece was measured. Next, the test piece was immersed in an electrolyte (volume ratio: a mixed solvent of ethylene carbonate / diethyl carbonate = 3 / 7, and LiPF 6 The test piece was then immersed in a mixed solvent (a solution in which the mixed solvent was dissolved) at a temperature of 60°C for 72 hours. After that, the test piece was taken out of the mixed solvent, the mixed solvent on the surface was wiped off, and the mass W3 (g) of the test piece was measured. The swelling degree (%) was calculated according to the following formula. Swelling degree (%) = W3 / W2 x 100

[0143] <Shape of adhesive material> The shape of the adhesive material applied to the bonding surfaces was observed using a laser microscope (Keyence Corporation, VR-3100).

[0144] <Adhesive material coverage> For each region, the basis weight of the adhesive material was calculated from the difference in mass per unit area before the adhesive composition was supplied and after the adhesive composition was supplied and dried.

[0145] <Adhesion between electrode and separator> Under the same conditions as in each of the examples and comparative examples, a negative electrode with an adhesive material applied on one side and a separator were pressed for 10 seconds under pressing conditions of a temperature of 70°C and a pressure of 1 MPa, and the laminate after bonding (i.e., a laminate in which one negative electrode and one separator are bonded together via the adhesive material) was sampled and used as a test specimen. The test piece was placed with the negative electrode current collector side facing down, and cellophane tape was attached to the surface of the negative electrode current collector side. The cellophane tape used was specified in JIS Z1522. The cellophane tape was fixed to a horizontal test table. One end of the separator was then pulled vertically upward at a pulling speed of 50 mm / min to measure the stress when it was peeled off. This measurement was performed a total of six times, and the average stress value was calculated as the peel strength, and the adhesion between the negative electrode and the separator was evaluated according to the following criteria: A higher peel strength indicates a higher adhesion between the electrode (negative electrode) and the separator. A: Peel strength is 1.5N / m or more B: Peel strength is 1.0N / m or more and less than 1.5N / m C: Peel strength is 0.5N / m or more and less than 1.0N / m D: Peel strength is less than 0.5N / m

[0146] <Cycle characteristics of secondary batteries> The lithium ion secondary batteries produced in the examples and comparative examples were left to stand at 25°C for 5 hours after injecting the electrolyte. Next, they were charged to a cell voltage of 3.65V at 25°C and 0.2C constant current, and then aged at 60°C for 12 hours. Then, they were discharged to a cell voltage of 3.00V at 25°C and 0.2C constant current. Then, they were CC-CV charged (upper cell voltage 4.30V) at 0.2C constant current, and CC discharged to 3.00V at 0.2C constant current. Thereafter, 100 cycles of charge and discharge were performed at a cell voltage of 4.30-3.00V and a charge and discharge rate of 1.0C in an environment of 45°C. The capacity at the first cycle, i.e., the initial discharge capacity X1, and the discharge capacity at the 100th cycle X2 were measured, and the capacity retention rate (%) = (X2 / X1) x 100 was calculated and evaluated according to the following criteria. The higher the capacity retention rate, the better the cycle characteristics of the secondary battery. A: Capacity retention rate is 90% or more B: Capacity retention rate is 85% or more but less than 90% C: Capacity retention rate is 80% or more but less than 85% D: Capacity retention rate is less than 80%

[0147] <Output characteristics> The fabricated lithium ion secondary battery was charged at constant current and constant voltage (CCCV) up to 4.3 V in an atmosphere at 25° C. to prepare a cell. The prepared cell was discharged to 3.0 V by a constant current method of 0.2 C and 1 C in an atmosphere at −10° C. to determine the electric capacity. Then, the discharge capacity retention rate expressed as the ratio of electric capacities (= (electric capacity at 1 C / electric capacity at 0.2 C)×100(%)) was determined. These measurements were performed on five lithium ion secondary battery cells, and the average value of the determined discharge capacity retention rate was evaluated as the output characteristic according to the following criteria. The larger this value, the more excellent the output characteristic. A: The average discharge capacity retention rate is 80% or more B: The average discharge capacity retention rate is 70% or more and less than 80% C: Average discharge capacity retention rate is 60% or more and less than 70% D: The average discharge capacity retention rate is less than 60%

[0148] (Production Example 1) <Production of Particulate Polymer 1> 100 parts of ion-exchanged water and 0.3 parts of ammonium persulfate were respectively supplied to a reactor equipped with a stirrer, the gas phase was replaced with nitrogen gas, and the temperature was raised to 80 ° C. Meanwhile, in another vessel, 40 parts of ion-exchanged water, 0.2 parts of sodium dodecylbenzenesulfonate as an emulsifier, 40.3 parts of styrene as an aromatic monovinyl monomer, 27.3 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acidic group-containing monomer, and 0.3 parts of ethylene glycol dimethacrylate as a crosslinkable monomer were mixed to obtain a monomer composition for forming a core part. This monomer composition for forming a core part was continuously added to the reactor over 3 hours and subjected to a polymerization reaction at a temperature of 80 ° C. The polymerization was continued until the polymerization conversion rate reached 95%, to obtain an aqueous dispersion containing a particulate polymer constituting the core part. Next, a monomer composition for forming a shell portion, which contains 29.7 parts of styrene as an aromatic monovinyl monomer and 0.3 parts of methacrylic acid as an acidic group-containing monomer, was continuously fed to this aqueous dispersion over 60 minutes to continue polymerization. When the polymerization conversion rate reached 98%, the reaction was stopped by cooling to prepare an aqueous dispersion containing particulate polymer 1. The volume average particle size, swelling degree, and glass transition temperature of the obtained particulate polymer 1 were measured. The results are shown in Table 1. In addition, by observing the cross-sectional structure of the particulate polymer using a transmission electron microscope (TEM), it was confirmed that the particulate polymer has a core-shell structure in which the shell part partially covers the outer surface of the core part.

[0149] (Production Example 2) <Production of Particulate Polymer 2> In the production of the particulate polymer of Production Example 1, instead of the core-forming monomer composition containing 40.3 parts of styrene as an aromatic monovinyl monomer, 27.3 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acidic group-containing monomer, and 0.3 parts of ethylene glycol dimethacrylate as a crosslinkable monomer, a core-forming monomer composition containing 17.0 parts of methyl methacrylate and 36.1 parts of butyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 14.0 parts of acrylonitrile as a (meth)acrylonitrile monomer, 2.8 parts of methacrylic acid as an acidic group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinkable monomer was used, except that an aqueous dispersion of particulate polymer 2 having a core-shell structure was prepared in the same manner as in Production Example 1. Then, various measurements were performed in the same manner as in Production Example 1. The results are shown in Table 1.

[0150] <Production of Particulate Polymer 3> In the production of the particulate polymer of Production Example 1, instead of the core-forming monomer composition containing 40.3 parts of styrene as an aromatic monovinyl monomer, 27.3 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acidic group-containing monomer, and 0.3 parts of ethylene glycol dimethacrylate as a crosslinkable monomer, a monomer composition containing 57.6 parts of styrene as an aromatic monovinyl monomer, 39.0 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 3.0 parts of methacrylic acid as an acidic group-containing monomer, and 0.4 parts of ethylene glycol dimethacrylate as a crosslinkable monomer was used, and a monomer composition for forming the shell portion was not supplied. An aqueous dispersion of particulate polymer 3 not having a core-shell structure was prepared in the same manner as in Production Example 1. Then, various measurements were performed in the same manner as in Production Example 1. The results are shown in Table 1.

[0151] (Production Example 4) <Production of Particulate Polymer 4> Into a reactor equipped with a stirrer, 90 parts of ion-exchanged water and 0.5 parts of ammonium persulfate were respectively supplied, the gas phase was replaced with nitrogen gas, and the temperature was raised to 80° C. Meanwhile, in another vessel, 15 parts of ion-exchanged water, 1.0 part of Neoperex G15 (manufactured by Kao Chemical Co., Ltd.) as an emulsifier, 70.0 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 25.0 parts of styrene as an aromatic monovinyl monomer, 1.7 parts of allyl glycidyl ether and 0.3 parts of allyl methacrylate as crosslinkable monomers, and 3.0 parts of acrylic acid as an acidic group-containing monomer were mixed to obtain a monomer composition. This monomer composition was continuously added to the reactor over 4 hours to carry out polymerization. During the continuous addition, the reaction was carried out at a temperature of 80° C. After the continuous addition was completed, the mixture was stirred at a temperature of 80° C. for an additional 3 hours to complete the reaction. The obtained aqueous dispersion was cooled to a temperature of 25° C., and then an aqueous sodium hydroxide solution was added thereto to adjust the pH to 8.0. Then, steam was introduced to remove unreacted monomers, thereby obtaining an aqueous dispersion of particulate polymer 4 not having a core-shell structure. Various measurements were then carried out in the same manner as in Production Example 1. The results are shown in Table 1.

[0152] (Production Example 5) In the production of the particulate polymer of Production Example 1, instead of the core-forming monomer composition containing 40.3 parts of styrene as an aromatic monovinyl monomer, 27.3 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acidic group-containing monomer, and 0.3 parts of ethylene glycol dimethacrylate as a crosslinkable monomer, a core-forming monomer composition containing 20.2 parts of styrene as an aromatic monovinyl monomer, 47.6 parts of 2-ethylhexyl acrylate as a monofunctional (meth)acrylic acid ester monomer, 2.1 parts of methacrylic acid as an acidic group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinkable monomer was used, and an aqueous dispersion of particulate polymer 5 having a core-shell structure was prepared in the same manner as in Production Example 1. Then, various measurements were performed in the same manner as in Production Example 1. The results are shown in Table 1.

[0153] (Production Example 6) In the production of the particulate polymer in Production Example 5, an aqueous dispersion of a particulate polymer 6 having a core-shell structure was prepared in the same manner as in Production Example 5, except that 100 parts of ion-exchanged water, 0.3 parts of ammonium persulfate, and 0.03 parts of sodium dodecylbenzenesulfonate as an emulsifier were supplied to a reactor equipped with a stirrer. Then, various measurements were carried out in the same manner as in Production Example 1. The results are shown in Table 1.

[0154] Example 1 <Preparation of Adhesive Composition> The aqueous dispersion of particulate polymer 1 obtained in Production Example 1 and the aqueous dispersion of particulate polymer 4 obtained in Production Example 4 were mixed so that the mass ratio of the solid contents was 100:10, and further, ion-exchanged water was added to dilute the mixture so that the solid content concentration was 10.5%. Propylene glycol was further added to the obtained mixture to adjust the solid content concentration to 10%, and an adhesive composition 1 was obtained.

[0155] <Preparation of negative electrode substrate> In a 5MPa pressure vessel equipped with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after thorough stirring, the temperature was heated to 50 ° C. to start polymerization. When the polymerization conversion rate reached 96%, the reaction was stopped by cooling to obtain a mixture containing a binder (SBR) for the negative electrode composite layer. A 5% aqueous sodium hydroxide solution was added to the mixture containing the binder for the negative electrode composite layer, and the pH was adjusted to 8, and unreacted monomers were removed by heating and reduced pressure distillation. Then, the mixture was cooled to a temperature of 30 ° C. or less to obtain an aqueous dispersion containing the desired binder for the negative electrode composite layer. Next, 100 parts of artificial graphite (volume average particle diameter: 15.6 μm) as a negative electrode active material, 1 part of a 2% aqueous solution of carboxymethylcellulose sodium salt (manufactured by Nippon Paper Industries Co., Ltd., product name "MAC350HC") as a viscosity modifier in terms of solid content, and ion-exchanged water were mixed to adjust the solid content concentration to 68%, and then further mixed at a temperature of 25 ° C. for 60 minutes. Furthermore, the solid content concentration was adjusted to 62% with ion-exchanged water, and then further mixed at a temperature of 25 ° C. for 15 minutes. 1.5 parts of the aqueous dispersion containing the binder for the negative electrode composite layer and ion-exchanged water were added to the obtained mixture, and the final solid content concentration was adjusted to 52%, and further mixed for 10 minutes. This was defoamed under reduced pressure to obtain a slurry composition for secondary battery negative electrodes with good fluidity. The obtained slurry composition for secondary battery negative electrode was applied to both sides of a 20 μm thick copper foil current collector with a comma coater so that the film thickness after drying was about 150 μm, and then dried. This drying was performed by conveying the copper foil at a speed of 0.5 m / min in an oven at a temperature of 60° C. for 2 minutes. Then, the copper foil was heated at a temperature of 120° C. for 2 minutes to obtain a negative electrode raw sheet before pressing. This negative electrode raw sheet before pressing was rolled with a roll press to obtain a negative electrode raw sheet after pressing with a negative electrode composite layer thickness of 80 μm.

[0156] <Preparation of positive electrode substrate> LiCoO with a volume average particle size of 12 μm as a positive electrode active material 2 100 parts of the above, 2 parts of acetylene black (manufactured by Denka Co., Ltd., product name "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (manufactured by Kureha Co., Ltd., product name "#7208") as a binder in terms of solid content, and N-methylpyrrolidone as a solvent were mixed to make the total solid content concentration 70%. These were mixed using a planetary mixer to obtain a slurry composition for secondary battery positive electrodes. The obtained slurry composition for secondary battery positive electrode was applied to both sides of a 20 μm thick aluminum foil current collector with a comma coater so that the film thickness after drying was about 150 μm, and then dried. This drying was performed by conveying the aluminum foil at a speed of 0.5 m / min in an oven at a temperature of 60° C. for 2 minutes. Then, the aluminum foil was heat-treated at a temperature of 120° C. for 2 minutes to obtain a positive electrode blank. The obtained positive electrode blank was then rolled using a roll press machine to obtain a pressed positive electrode blank having a positive electrode mixture layer.

[0157] <Preparing the separator roll> A separator substrate made of polypropylene (PP) (product name: Celgard 2500) was prepared.

[0158] <Production of Laminate> Using the adhesive composition thus prepared, the negative electrode raw sheet, the positive electrode raw sheet, and the separator raw sheet, a laminate was prepared as shown in Fig. 11. In Fig. 11, reference numeral 91 denotes a transport roller, and reference numeral 92 denotes a heat roller. Specifically, while conveying the negative electrode raw roll 20A unwound from the negative electrode raw roll at a speed of 10 m / min, an adhesive composition was supplied from an inkjet head of an inkjet coating machine 52 (Konica, KM1024 (shear mode type)) onto one surface of the negative electrode raw roll 20A, and the second separator raw roll 30A unwound from the separator raw roll and the negative electrode raw roll 20A were bonded together with pressure rollers 61 and 62. Also, an adhesive composition was supplied from an inkjet head of an inkjet coating machine 51 (Konica, KM1024 (shear mode type)) onto the other surface of the negative electrode raw roll 20A, and the first separator raw roll 10A unwound from the separator raw roll and the laminate of the negative electrode raw roll 20A and the second separator raw roll 30A were bonded together with pressure rollers 61 and 62. Further, an adhesive composition was supplied from the inkjet head of an inkjet coater 53 (Konica, KM1024 (shear mode type)) to the surface of the first separator raw roll 10A opposite to the negative electrode raw roll 20A side, and the previously cut positive electrode 40 was placed on it. The laminate of the first separator raw roll 10A, the negative electrode raw roll 20A, and the second separator raw roll 30A and the positive electrode 40 were bonded with pressure rollers 61 and 62. Then, an adhesive composition was supplied from the inkjet head of an inkjet coater 54 (Konica, KM1024 (shear mode type)) onto the positive electrode 40, and the laminate was cut with a cutter 70 to obtain a laminate in which the second separator, the negative electrode, the first separator, and the positive electrode were laminated in this order. The bonding using pressure rollers 61 and 62 was performed at a temperature of 70° C. and a pressure of 1 MPa. Furthermore, the supplied adhesive composition was dried by using a heat roller 92 as a part of the conveying roller 91 (drying temperature: 70° C., drying time: 1 second).

[0159] Here, the adhesive composition was supplied from the coaters 51 to 54 as shown in Table 2. Specifically, a region having a center at the same position as the center of the bonding surfaces X, Y between the electrode and the separator, a shape similar to the shape of the bonding surfaces X, Y, and an area of ​​10% of the area of ​​the bonding surfaces X, Y is defined as a "region S where the adhesive material is densely applied" in Table 2, and a region other than the "region S where the adhesive material is densely applied" of the bonding surfaces X, Y is defined as a "region T where the adhesive material is sparsely applied", with a "coverage rate of the adhesive material" of 3.0% and a "basis weight of the adhesive material" of 0.180 g / m in the "region S where the adhesive material is densely applied". 2 The "coverage rate of adhesive material" in the "area T where adhesive material is sparsely applied" is 0.79%, and the "basis weight of adhesive material" is 0.044 g / m 2 The adhesive layer composition was applied (supplied) so that the adhesive layer composition was as follows. The "adhesive material" in the "coverage rate of the adhesive material" and the "basis weight of the adhesive material" refers to the adhesive composition in a state in which the adhesive composition has been dried and the solvent has been removed. The adhesive composition 1 described above was used as the adhesive composition to be applied in both the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied". In both the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied", the adhesive composition was applied in a dot pattern. When the adhesive composition after drying (the adhesive material as a dried product) was observed with a laser microscope, a plurality of adhesive materials arranged in a fine dot pattern were present on the bonding surface. In both the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied", the dot size of the adhesive material arranged in a dot pattern was 40 μm in diameter.

[0160] By applying the adhesive material as described above, the adhesive material coverage E in the central region P, which has a center at the same position as the center of the bonding surfaces X, Y between the electrode and the separator, a shape similar to the shape of the bonding surfaces X, Y, and an area of ​​10% of the area of ​​the bonding surfaces X, Y, is 3.0%, and the adhesive material basis weight is 0.180 g / m. 2 The adhesive coverage F of the bonding surfaces X and Y in the other regions Q other than the central region P is 0.79%, and the adhesive mass is 0.044 g / m 2 It became. The adhesive strength of the laminate was then evaluated, and the results are shown in Table 2.

[0161] <Manufacture of secondary batteries and measurement of resistance per unit area> The laminate was wrapped in an aluminum packaging material as an exterior, and an electrolyte solution (solvent: ethylene carbonate / diethyl carbonate / vinylene carbonate = 68.5 / 30 / 1.5 (volume ratio), electrolyte: LiPF with a concentration of 1M) was added. 6 ) was injected. The opening of the aluminum packaging exterior was then closed with a heat seal at a temperature of 150°C to produce a lithium-ion secondary battery. After the electrolyte was injected, the battery was left to stand at a temperature of 25°C for 5 hours. Next, the battery was charged to a cell voltage of 3.65V at a constant current of 0.2C at a temperature of 25°C, and then aged at a temperature of 60°C for 12 hours. Then, the battery was discharged to a cell voltage of 3.00V at a constant current of 0.2C at a temperature of 25°C. Then, the battery was CC-CV charged (upper cell voltage 4.30V) at a constant current of 0.2C, and CC discharged to 3.00V at a constant current of 0.2C. After that, the battery was charged to a SOC (State Of Charge): 50% and disassembled in an inert gas atmosphere. 2Five electrode groups were randomly punched out so that the electrode group was equal to or smaller than the center region P. After joining tab leads to each, they were wrapped in an aluminum packaging exterior as an exterior material, and the above-mentioned electrolyte was poured into them to produce five secondary batteries consisting only of the center region P. The produced batteries were discharged at a discharge rate of 3C for a discharge time of 10 seconds, and the average value of the DC resistance was taken as the resistance A per unit area of ​​the center region P. Note that the "DC resistance" referred to here refers to the resistance value calculated by the following formula when the voltage before discharge (0 seconds) is V0 and the voltage after 10 seconds is V1. DC resistance=1cm 2 × (V1-V0) / 3C current value In addition, as described above, 10 electrode groups were randomly punched out from the other region Q other than the central region P of the disassembled laminate so that the effective area was 1 cm × 1 cm, and a secondary battery consisting of only the other region Q was fabricated in the same manner. The average DC resistance value when the fabricated battery was discharged under the same conditions as described above was taken as the resistance B per unit area of ​​the other region Q, and the resistance value ratio (A / B) is shown in Table 2.

[0162] In addition, five of the laminates prepared above were stacked together and pressed at a temperature of 70° C. and a pressure of 1 MPa for 10 seconds to produce a stacked body, which was then wrapped in an aluminum packaging exterior as an exterior and filled with an electrolyte (solvent: ethylene carbonate / diethyl carbonate / vinylene carbonate = 68.5 / 30 / 1.5 (volume ratio), electrolyte: LiPF with a concentration of 1M). 6 ) was poured into the battery. The opening of the aluminum packaging was then closed by heat sealing at a temperature of 150°C to produce a stacked lithium-ion secondary battery with a capacity of 800 mAh. The cycle characteristics and output characteristics of the resulting secondary battery were evaluated. The results are shown in Table 2.

[0163] Example 2 In the production of the laminate of Example 1, the area of ​​the "region S where the adhesive material is densely applied" was changed from 10% to 20% of the area of ​​the bonding surfaces X and Y, and the area of ​​the "region T where the adhesive material is sparsely applied" was changed from 90% to 80% of the area of ​​the bonding surfaces X and Y. Except for this, the adhesive composition, the negative electrode raw material, the positive electrode raw material, the separator raw material, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2. In addition, due to the change in the areas of the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied", the above-mentioned central region P consists only of the "region S where the adhesive material is densely applied". Therefore, the coverage E of the adhesive material in the central region P is 3.0%, and the basis weight of the adhesive material is 0.180 g / m 2 However, in the other area Q, there is a mixture of an area corresponding to the "area S where the adhesive material is densely applied" and an area corresponding to the "area T where the adhesive material is sparsely applied", so the coverage rate F of the adhesive material in the other area Q is 1.04%, and the basis weight of the adhesive material is 0.059 g / m 2 In addition, when the other area Q includes a portion corresponding to the "area S where the adhesive material is densely applied" and a portion corresponding to the "area T where the adhesive material is sparsely applied," the coverage rate F and basis weight of the adhesive material in the other area Q can be calculated by the following formula. (Coverage rate F) = (Coverage rate of adhesive material in area S where adhesive material is densely applied) x (Ratio of area S where adhesive material is densely applied to other areas Q) + (Coverage rate of adhesive material in area T where adhesive material is sparsely applied) x (Ratio of area T where adhesive material is sparsely applied to other areas Q) (Balance weight) = (Balance weight of adhesive material in area S where adhesive material is densely applied) x (ratio of area S where adhesive material is densely applied to other areas Q) + (Balance weight of adhesive material in area T where adhesive material is sparsely applied) x (ratio of area T where adhesive material is sparsely applied to other areas Q)

[0164] Example 3 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in dot form to the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied" was adjusted to change the dot size of the adhesive composition supplied in dot form from a diameter of 40 μm to a diameter of 80 μm without changing the coverage of the adhesive material in each of the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied". As a result, the basis weight of the adhesive material in the "region S where the adhesive material is densely applied" was 0.124 g / m 2 The adhesive material coating weight in the "region T where the adhesive material is sparsely applied" is 0.031 g / m 2 Thereafter, in the same manner as in Example 1, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0165] Example 4 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in dot form to the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied" was adjusted to change the dot size of the adhesive composition supplied in dot form from a diameter of 40 μm to a diameter of 20 μm without changing the coverage of the adhesive material in each of the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied". As a result, the basis weight of the adhesive material in the "region S where the adhesive material is densely applied" was 0.158 g / m 2 The adhesive material coating weight in the "region T where the adhesive material is sparsely applied" is 0.040 g / m 2 Thereafter, in the same manner as in Example 1, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0166] Example 5 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region T where the adhesive material is sparsely applied" was adjusted to change the coverage of the adhesive material in the "region T where the adhesive material is sparsely applied" from 0.79% to 0.35%, and the basis weight of the adhesive material was changed to 0.044 g / m 2 from 0.022 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0167] Example 6 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region T where the adhesive material is sparsely applied" was adjusted to change the coverage of the adhesive material in the "region T where the adhesive material is sparsely applied" from 0.79% to 0.20%, and the basis weight of the adhesive material was changed to 0.044 g / m 2 from 0.011 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0168] Example 7 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region T where the adhesive material is sparsely applied" was adjusted to change the coverage of the adhesive material in the "region T where the adhesive material is sparsely applied" from 0.79% to 1.40%, and the basis weight of the adhesive material was changed to 0.044 g / m 2 from 0.079 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0169] Example 8 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region S where the adhesive material is densely applied" was adjusted to change the coverage of the adhesive material in the "region S where the adhesive material is densely applied" from 3.00% to 5.60%, and the basis weight of the adhesive material was changed to 0.180 g / m 2 from 0.316 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0170] Example 9 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region S where the adhesive material is densely applied" was adjusted to change the coverage of the adhesive material in the "region S where the adhesive material is densely applied" from 3.00% to 12.57%, and the basis weight of the adhesive material was changed to 0.180 g / m 2 from 0.712 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0171] Example 10 In the production of the laminate of Example 1, the center-to-center distance (pitch) of the adhesive composition supplied in the form of dots to the "region S where the adhesive material is densely applied" was adjusted to change the coverage of the adhesive material in the "region S where the adhesive material is densely applied" from 3.00% to 1.40%, and the basis weight of the adhesive material was changed to 0.180 g / m 2 from 0.079 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0172] Example 11 In the production of the laminate of Example 1, the shape of the adhesive composition supplied in the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied" was changed from dots to stripes, the coverage of the adhesive material in the "region S where the adhesive material is densely applied" was changed from 3.00% to 9.09%, and the basis weight of the adhesive material was changed to 0.180 g / m 2 from 0.400 g / m 2 The coverage rate of the adhesive material in the "region T where the adhesive material is sparsely applied" was changed from 0.79% to 3.61%, and the basis weight of the adhesive material was changed to 0.044 g / m 2 From 0.100 g / m 2 Except for the above change, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0173] Example 12 In the production of the laminate of Example 1, the adhesive composition to be applied to the "area S where the adhesive material is densely applied" and the "area T where the adhesive material is sparsely applied" was changed from the adhesive composition 1 prepared in Production Example 1 to the adhesive composition 4 prepared as described below. In the same manner as in Example 1, except for this, the adhesive composition, the negative electrode raw sheet, the positive electrode raw sheet, the separator raw sheet, the laminate, and the secondary battery were produced and prepared. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2. <Preparation of Adhesive Composition 4> 5 parts of sodium dodecylbenzenesulfonate was added to 100 parts of ion-exchanged water and stirred with a disperser, and 10 parts of vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP; "LBG" manufactured by Arkema) powder was gradually added and stirred for 2 hours to obtain an aqueous dispersion of PVdF-HFP with a solid content concentration of 10.5%. Propylene glycol was further added to the obtained aqueous dispersion to adjust the solid content concentration to 10%, and adhesive composition 4 was obtained.

[0174] Example 13 In the production of the laminate of Example 1, the area of ​​the "region S where the adhesive material is densely applied" was changed from 10% to 50% of the area of ​​the bonding surfaces X and Y, and the area of ​​the "region T where the adhesive material is sparsely applied" was changed from 90% to 50% of the area of ​​the bonding surfaces X and Y. Except for this, the adhesive composition, the negative electrode raw material, the positive electrode raw material, the separator raw material, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2. In addition, due to the change in the areas of the "region S where the adhesive material is densely applied" and the "region T where the adhesive material is sparsely applied", the above-mentioned central region P consists only of the "region S where the adhesive material is densely applied". Therefore, the coverage E of the adhesive material in the central region P is 3.0%, and the basis weight of the adhesive material is 0.180 g / m 2 However, in the other area Q, there is a mixture of an area corresponding to the "area S where the adhesive material is densely applied" and an area corresponding to the "area T where the adhesive material is sparsely applied", so the coverage rate F of the adhesive material in the other area Q is 1.77%, and the basis weight of the adhesive material is 0.104 g / m 2 It became.

[0175] Example 14 In the production of the laminate of Example 1, a "coated area S1" was used instead of the "area S where the adhesive material is densely coated", and the adhesive material coverage rate was 3.00% and the basis weight was 0.180 g / cm in the "coated area S1". 2The adhesive composition 2 prepared as described below was applied so that the adhesive composition 2 was applied to the bonding surfaces X and Y. The bonding surfaces X and Y were then coated with the adhesive composition 2 so that the adhesive composition 2 was applied to the bonding surfaces X and Y. The bonding surfaces X and Y were then coated with the adhesive composition 2 so that the adhesive composition 2 was applied to the bonding surfaces X and Y. The bonding surfaces X and Y were then coated with the adhesive composition 2 so that the adhesive composition 2 was applied to the bonding surfaces X and Y. The bonding surface was ... 2 The adhesive composition, the negative electrode raw sheet, the positive electrode raw sheet, the separator raw sheet, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1, except that the adhesive composition 1 was applied so as to obtain the following: Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 3. <Preparation of Adhesive Layer Composition 2> In the preparation of the adhesive layer composition of Example 1, the aqueous dispersion of the particulate polymer 2 having a core-shell structure obtained in Production Example 2 was used instead of the aqueous dispersion of the particulate polymer 1 having a core-shell structure obtained in Production Example 1, and the adhesive composition 2 was obtained in the same manner as in Example 1.

[0176] Example 15 In the production of the laminate of Example 1, a "coated area S1" was used instead of the "area S where the adhesive material is densely coated", and the adhesive material coverage rate was 3.00% and the basis weight was 0.180 g / cm in the "coated area S1". 2 The adhesive composition 3 prepared as described below was applied so that the adhesive composition 3 was applied to the bonding surfaces X and Y. The bonding surfaces X and Y were then coated with the adhesive composition 3. The bonding composition 3 was applied to the bonding surfaces X and Y ... 2 The adhesive composition, the negative electrode raw sheet, the positive electrode raw sheet, the separator raw sheet, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1, except that the adhesive composition 1 was applied so as to obtain the following: Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 3. <Preparation of Adhesive Layer Composition 3> In preparing the adhesive layer composition of Example 1, the aqueous dispersion of the particulate polymer 3 not having a core-shell structure obtained in Production Example 3 was used in place of the aqueous dispersion of the particulate polymer 1 having a core-shell structure obtained in Production Example 1, and the adhesive composition 3 was obtained in the same manner as in Example 1.

[0177] (Example 16) In the production of the laminate of Example 1, the adhesive composition to be applied to the "area S where the adhesive material is densely applied" and the "area T where the adhesive material is sparsely applied" was changed from the adhesive composition 1 prepared in Production Example 1 to the adhesive composition 5 prepared as described below. In the same manner as in Example 1, except for this, the adhesive composition, the negative electrode raw sheet, the positive electrode raw sheet, the separator raw sheet, the laminate, and the secondary battery were produced and prepared. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 4. <Preparation of Adhesive Layer Composition 5> In preparing the adhesive layer composition of Example 1, the aqueous dispersion of the particulate polymer 5 having a core-shell structure obtained in Production Example 5 was used instead of the aqueous dispersion of the particulate polymer 1 having a core-shell structure obtained in Production Example 1, and the adhesive composition 5 was obtained in the same manner as in Example 1.

[0178] (Example 17) In the production of the laminate of Example 1, the adhesive composition to be applied to the "area S where the adhesive material is densely applied" and the "area T where the adhesive material is sparsely applied" was changed from the adhesive composition 1 prepared in Production Example 1 to the adhesive composition 6 prepared as described below. In the same manner as in Example 1, except for this, the adhesive composition, the negative electrode raw material, the positive electrode raw material, the separator raw material, the laminate, and the secondary battery were produced and prepared. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 4. <Preparation of Adhesive Layer Composition 6> In the preparation of the adhesive layer composition of Example 1, the aqueous dispersion of the particulate polymer 6 having a core-shell structure obtained in Production Example 6 was used instead of the aqueous dispersion of the particulate polymer 1 having a core-shell structure obtained in Production Example 1, and the adhesive composition 6 was obtained in the same manner as in Example 1.

[0179] Comparative Example 1 A gravure coater was used as the coater 51 to 54 instead of the inkjet coater, and the adhesive composition 1 was applied to the entire bonding surface, so that the coverage rate of the adhesive material on the entire bonding surface X, Y was 90%, and the basis weight of the adhesive material was 0.220 g / m 2 Except for the above, an adhesive material, an adhesive composition, a negative electrode raw sheet, a positive electrode raw sheet, a separator raw sheet, a laminate, and a secondary battery were produced and prepared in the same manner as in Example 1. Then, various evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0180] Comparative Example 2 In the production of the laminate of Example 1, the area of ​​the "region S where the adhesive material is densely applied" was changed from 10% to 100% of the area of ​​the bonding surfaces X and Y, and the area of ​​the "region T where the adhesive material is sparsely applied" was changed from 90% to 0% of the area of ​​the bonding surfaces X and Y. Except for this, the adhesive composition, the negative electrode raw material, the positive electrode raw material, the separator raw material, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0181] Comparative Example 3 In the production of the laminate of Example 1, the area of ​​the "region S where the adhesive material is densely applied" was changed from 10% to 0% of the area of ​​the bonding surfaces X and Y, and the area of ​​the "region T where the adhesive material is sparsely applied" was changed from 90% to 100% of the area of ​​the bonding surfaces X and Y. Except for this, the adhesive composition, the negative electrode raw material, the positive electrode raw material, the separator raw material, the laminate, and the secondary battery were produced and prepared in the same manner as in Example 1. Then, various measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 2.

[0182] In addition, in Tables 1 to 4, "MMA" indicates methyl methacrylate, "BA" indicates butyl acrylate, "2EHA" indicates 2-ethylhexyl acrylate, "AN" indicates acrylonitrile, "St" indicates styrene, "MAA" stands for methacrylic acid; "AA" represents acrylic acid, "AGE" stands for allyl glycidyl ether. "AMA" stands for allyl methacrylate; "EDMA" refers to ethylene glycol dimethacrylate. Also, in Table 2, "PVdF-HFP" refers to vinylidene fluoride-hexafluoropropylene copolymer.

[0183] [Table 1]

[0184] [Table 2]

[0185] [Table 3]

[0186] [Table 4]

[0187] From Tables 2, 3, and 4, it can be seen that the secondary batteries of Examples 1 to 17, which have a laminate formed by stacking a positive electrode, a separator, and a negative electrode in this order, and which have a shape similar to the shape of surface Z which is at least one of the bonding surface X between the positive electrode and the separator and the bonding surface Y between the negative electrode and the separator, have a center at the same position as the center of surface Z, and have an area of ​​10% of the area of ​​surface Z, have a resistance A per unit area of ​​a central region P greater than the resistance B per unit area of ​​a region Q other than the central region P on surface Z, have excellent cycle characteristics. On the other hand, in Comparative Examples 1 to 3 in which the resistance A per unit area of ​​the central region P is not larger than the resistance B per unit area of ​​the region Q other than the central region P on the surface Z, the cycle characteristics of the secondary battery are inferior. [Industrial Applicability]

[0188] According to the present invention, a secondary battery having excellent cycle characteristics can be provided. [Explanation of symbols]

[0189] 10 First separator 10A First separator roll 20 negative electrode 20A negative electrode material 21 Negative electrode current collector 22,23 Negative electrode composite layer 24 First edge 25 Second edge 26 Third edge 27 Fourth edge 30 Second separator 30A Second separator roll 40 positive electrode 41 Positive electrode current collector 42, 43 Positive electrode composite layer 50 droplets 51~54 Coating machine (nozzle head) 55 Nozzle 60 Base material 61,62 Pressure roller 70 cutting machine 91 Conveyor roller 92 Heat Roller Z plane R center P central area Q Other Areas r Radius of the dot x,y distance between dot centers l Line width of the coated area s Interval between coated areas (line width of uncoated areas) S Area where adhesive material is applied densely T1 Area where adhesive material is applied sparsely T2: Area where adhesive material is applied more sparsely T3: Area where adhesive material is applied more sparsely 100,100A laminate 200 Superimposed Body 300 Particulate polymer 310 Core 310S Core outer surface 320 Shell

Claims

1. A secondary battery having a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order, a central region P having a shape similar to the shape of a surface Z which is at least one of a bonding surface X between the positive electrode and the separator and a bonding surface Y between the negative electrode and the separator, a center at the same position as the center of the surface Z, and an area of ​​10% of the area of ​​the surface Z, has a resistance A per unit area larger than a resistance B per unit area of ​​a region Q of the surface Z other than the central region P, An adhesive material is present on said surface Z; The coverage of the adhesive material on the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z. Secondary battery.

2. A secondary battery as described in claim 1, wherein the coverage rate E of the adhesive material in the central region P of the surface Z is greater than the coverage rate F of the adhesive material in a region Q other than the central region P of the surface Z.

3. The secondary battery according to claim 2 , wherein the coverage E is 1.1% or more and 30% or less.

4. The secondary battery according to claim 2 , wherein the coverage F is equal to or greater than 0.3% and less than 0.4×E%.

5. The adhesive material comprising a particulate polymer; 5. The secondary battery according to claim 1, wherein the particulate polymer has a core-shell structure comprising a core portion and a shell portion partially covering an outer surface of the core portion.

6. A method for producing a secondary battery having a laminate in which a positive electrode, a separator, and a negative electrode are laminated in this order, comprising the steps of: The method includes a step of applying an adhesive material to a surface Z which is at least one of a bonding surface X between the positive electrode and the separator and a bonding surface Y between the negative electrode and the separator, a coverage rate E of the adhesive material in a central region P having a shape similar to the shape of the surface Z, a center at the same position as the center of the surface Z, and an area of ​​10% of the area of ​​the surface Z is greater than a coverage rate F of the adhesive material in a region Q other than the central region P of the surface Z, and the coverage rate of the adhesive material in the surface Z gradually decreases from the center of the surface Z toward the periphery of the surface Z; and A resistance A per unit area of ​​the central region P is greater than a resistance B per unit area of ​​the region Q. A method for manufacturing a secondary battery.

7. The method for producing a secondary battery according to claim 6 , wherein the coverage E is 1.1% or more and 30% or less.

8. The method for producing a secondary battery according to claim 6 or 7, wherein the coverage F is 0.3% or more and less than 0.4×E%.

9. the adhesive material comprises a particulate polymer; 9. The method for producing a secondary battery according to claim 6, wherein the particulate polymer has a core-shell structure including a core portion and a shell portion partially covering an outer surface of the core portion.

Citation Information

Patent Citations

  • Nonaqueous electrolytic secondary battery

    JP1992308654A

  • Secondary battery

    JP2002184468A

  • Lamination structure cell

    JP2013191389A

  • Method for manufacturing secondary battery

    JP2016177962A

  • Separator for nonaqueous electrolyte secondary battery and manufacturing method for the same

    JP2016201327A